Inspection patch
By designing an examination patch with high transmittance and scanning performance, the problem of reduced image accuracy caused by probe scanning deviation was solved, achieving higher scanning and diagnostic accuracy.
Patent Information
- Application Number
- CN201980060864.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-25
- Filing Date
- 2019-09-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2039-09-20
AI Technical Summary
In microwave mammography, inaccurate scanning distances due to probe scanning deviations lead to reduced accuracy in three-dimensional images and diagnostic accuracy.
Design an examination patch with a basement membrane that has a transmittance of over 70%, displays scanning indicators, and can deform according to shape to help examiners accurately scan the breast and reduce microwave attenuation caused by probe oscillation.
It improves scanning accuracy and image diagnostics, reduces scanning omissions and repetitions, and enhances the quality of 3D images.
Smart Images

Figure CN112996438B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an inspection patch for image diagnosis using microwaves. Background Art
[0002] Mammography using microwaves has been proposed as a method for detecting breast cancer (for example, see Patent Document 1). In mammography using microwaves, there is no need to compress the breast to be examined, so the examinee does not feel pain during the examination. In addition, mammography using microwaves does not use X-rays, so the examinee is not exposed to X-rays.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2017 / 057524 Summary of the invention
[0006] Problems to be Solved by the Invention
[0007] However, in mammography using microwaves, a probe is used to scan the breast to generate a three-dimensional image. Then, based on the generated three-dimensional image, a diagnosis of breast cancer is made. In order to generate a more accurate three-dimensional image based on the subject's breast, it is required that the probe scan a predetermined distance each time, and scan the breast in a manner that does not omit or repeat the scan. However, since the scanning of the probe is performed manually by the examiner, deviations in the scanning distance, omissions in scanning, or duplications in scanning may occur. As a result, the accuracy of the three-dimensional image is reduced, resulting in a reduction in the accuracy of image diagnosis.
[0008] It should be noted that the above situation is not limited to mammography using microwaves, but is also common in image diagnosis of other inspection objects using microwaves.
[0009] An object of the present invention is to provide a patch for inspection that can improve the accuracy of image diagnosis.
[0010] Means for solving problems
[0011] A patch for inspection for solving the above-mentioned problems is used for image diagnosis using microwaves and comprises a patch body attached to an inspection object. The patch body is configured to display an index for scanning the inspection object on the patch body, deform according to the shape of the inspection object, and have a transmittance of 70% or more with respect to microwaves with a frequency of 2 GHz.
[0012] According to the above structure, the inspection implementer can be prompted to scan according to the index displayed on the patch body, thereby improving the scanning accuracy of the inspection object. In addition, the patch body has a transmittance of more than 70% with respect to microwaves with a frequency of 2 GHz, so the attenuation of microwaves caused by the oscillation of the probe can also be suppressed. As a result, the accuracy of the image obtained as the scanning result is improved, and as a result, the accuracy of the image diagnosis is improved.
[0013] A patch for inspection for solving the above-mentioned problems is a patch for inspection for image diagnosis using microwaves. It has a base film with scanning indicators and is attached to the inspection object. The base film has a tensile elongation at break of more than 130% and a 100% tensile strength of less than 4N / cm.
[0014] According to the above structure, the person implementing the inspection can be prompted to scan according to the index displayed on the patch body, thereby improving the scanning accuracy of the inspection object. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] [ Figure 1 ] is a cross-sectional view showing the structure of the first example of the inspection patch in the first embodiment.
[0016] [ Figure 2 ] is a cross-sectional view showing the structure of a second example of the inspection patch in the first embodiment.
[0017] [ Figure 3 ] represents a plan view of the structure of the inspection patch in a plan view relative to the surface of the inspection patch.
[0018] [ Figure 4 ] is a cross-sectional view showing the structure of the patch body when the inspection patch of the first example is used.
[0019] [ Figure 5 ] is a cross-sectional view showing the structure of the patch body when the inspection patch of the second example is used.
[0020] [ Figure 6 ] Schematic diagram for explaining how to use the inspection patch.
[0021] [ Figure 7 ] is a table showing the measurement results of the test examples of the first embodiment.
[0022] [ Figure 8 ] is a cross-sectional view showing the structure of the fourth example of the inspection patch in the second embodiment.
[0023] [ Fig. 9 ] represents the structure of the stacked body when the inspection patch of the second example is used.
[0024] [ Fig.10] Schematic diagram for explaining how to use the inspection patch.
[0025] [ Fig.11 ] is a table showing the measurement results and evaluation results of the test examples of the second embodiment.
[0026] [ Fig.12 ] is a table showing the measurement results and evaluation results of the test examples of the third embodiment.
[0027] [ Fig.13 ] is a table showing the measurement results and evaluation results of the test examples of the third embodiment.
[0028] [ Fig.14 ] is a process diagram for illustrating a process in a method for manufacturing a test patch in a fourth embodiment.
[0029] [ Fig.15 ] is a process diagram for illustrating a process in a method for manufacturing a test patch in a fourth embodiment.
[0030] [ Fig.16 ] is a process diagram for illustrating a process in a method for manufacturing a test patch in a fourth embodiment.
[0031] [ Fig.17 ] is a table showing the measurement results of the test examples of the fourth embodiment.
[0032] [ Fig.18 ] is a table showing the measurement results and evaluation results of the test examples of the fifth embodiment.
[0033] [ Fig.19 ] is a table showing the measurement results and evaluation results of the test examples of the sixth embodiment. DETAILED DESCRIPTION
[0034] [First embodiment]
[0035] Reference Figures 1 to 7 , a first embodiment of the inspection patch is described. The inspection patch, the method of using the inspection patch, and the test example are described in sequence below. In this embodiment, the inspection patch is a patch for mammography, which is an example of image diagnosis using microwaves. In mammography, the inspection patch is a patch attached to the breast as the inspection object.
[0036] [Inspection patch]
[0037] Reference Figures 1 to 3 , the inspection patch is explained.
[0038] The patch for examination includes a patch body. The patch body is configured to display an index for scanning the breast and to deform according to the shape of the breast. The patch body is attached to the breast. The transmittance of the patch body to microwaves with a frequency of 2 GHz is 70% or more. Figure 1 The structure of the first example of the inspection patch is explained and referenced Figure 2 The structure of the second example of the inspection patch is described. Figure 3 The common configuration of the first example of the inspection patch and the second example of the inspection patch will be described.
[0039] like Figure 1 As shown, the first example of the inspection patch 10 includes a base film 11 as an example of a patch body 10A. The base film 11 has a coordinate grid 12 for guiding the scanning position in the inspection object. The coordinate grid 12 is an example of a scanning index. In the base film 11, the transmittance to 2 GHz microwaves is 70% or more.
[0040] The microwave transmittance T is calculated by the following formula.
[0041] Transmittance T = (measured intensity μ m / reference strength μ0)×100
[0042] The reference intensity μ0 refers to the intensity of microwaves measured when a transmitter oscillating 2 GHz microwaves is in contact with a microwave receiver (mW / cm 2 ). Determine the intensity μ m It refers to the intensity of microwaves (mW / cm2) measured when the reference intensity μ0 is measured with the patch body 10A sandwiched between the same transmitter and receiver. 2 ).
[0043] According to the inspection patch 10, the inspection implementer such as a doctor or an inspection technician can be prompted to scan according to the index displayed on the patch body 10A. As a result, the scanning accuracy of the breast can be improved. In addition, the patch body 10A has a transmittance of more than 70% with respect to 2 GHz microwaves, so the attenuation of microwaves caused by the oscillation of the probe can also be suppressed. As a result, the accuracy of the image obtained as the scanning result is improved, and as a result, the accuracy of the image diagnosis is improved.
[0044] The patch body 10A has the coordinate grid 12, so there is no need for processing and tools for displaying indicators on the patch body 10A. In addition, the inspection implementer can use a probe to scan along the coordinate grid 12. Therefore, the inspection implementer can keep the distance of the probe scanning at a certain distance.
[0045] The patch body 10A includes a portion having a total light transmittance of 30% or more as specified in JIS K 7361-1:1997. Therefore, the state of the surface of the breast can be grasped through the portion of the patch body 10A having a total light transmittance of 30% or more. In the present embodiment, in the patch body 10A, the portion outside the coordinate grid 12 is a transmission portion having a total light transmittance of 30% or more. Therefore, the position of a mole or spot in the breast can be determined visually or by a camera through the transmission portion. Since the position of a mole or spot in the breast does not change, the position of the mole or spot in the breast is important when determining the position of a lesion in the breast.
[0046] The base film 11 is made of a synthetic resin. The synthetic resin used to form the base film 11 may be, for example, a polyurethane resin. Thus, a base film 11 having high lamination adaptability and high moisture permeability can be obtained. The thickness of the base film 11 may be, for example, 5 μm to 30 μm. For a thin base film 11 made of a polyurethane resin, the base film 11 can be well stretched even when the external force applied to the base film 11 for stretching the base film 11 is small. Therefore, the base film 11 has high tracking properties to the shape of the breast and has high adhesion to the breast.
[0047] It should be noted that as long as the transmittance of the base film 11 to 2 GHz microwaves is 70% or more, it may be formed of a synthetic resin other than polyurethane resin. Examples of synthetic resins other than polyurethane resins include polyvinylidene fluoride resins, ethylene-vinyl acetate copolymer resins, polypropylene resins, and polyethylene terephthalate resins.
[0048] The base film 11 includes a surface 11F and a back surface 11R as a pair of surfaces facing each other. The surface 11F is a surface that is scanned by a probe when inspecting an inspection object. In the present embodiment, the coordinate grid 12 is located on the back surface 11R.
[0049] The inspection patch 10 further includes a separation film 13 and a protective film 14. The separation film 13 is laminated on the front surface 11F of the base film 11 in a peelable manner. The protective film 14 is laminated on the back surface 11R of the base film 11 in a peelable manner.
[0050] The protective film 14 covers the back surface 11R of the base film. Therefore, by sandwiching the coordinate grid 12 between the base film 11 and the protective film 14, the coordinate grid 12 will not be exposed to the outer surface of the inspection patch 10. As a result, the coordinate grid 12 is difficult to peel off from the base film 11. When viewed from the direction in which the protective film 14 overlaps the base film 11, that is, when viewed from the direction opposite to the base film 11, the protective film 14 covers the entire base film 11. In the protective film 14, the surface in contact with the base film 11 is the surface 14F, and the surface opposite to the surface 14F is the back surface 14R. The protective film 14 covers the entire coordinate grid 12, and has a thickness that makes the back surface 14R a substantially flat surface.
[0051] In the inspection patch 10, the back side 11R of the base film 11 is attached to the subject. In the inspection patch 10, the base film 11 is sandwiched between the separation film 13 and the protection film 14 in the thickness direction of the base film 11. Therefore, until immediately before the base film 11 is attached to the subject, the base film 11 is protected from the outside by the separation film 13 and the protection film 14. Thus, the base film 11 is kept clean until it is attached to the subject.
[0052] The separation film 13 and the protective film 14 are preferably films made of transparent or translucent synthetic resins. The separation film 13 and the protective film 14 are, for example, formed by a substrate film and an anti-adhesive layer. The anti-adhesive layer is stacked on the substrate film. The anti-adhesive layer of the separation film 13 contacts the surface 11F of the substrate film 11. In addition, the anti-adhesive layer of the protective film 14 contacts the back side 11R of the substrate film 11. The substrate film may be, for example, a polyethylene terephthalate film, etc. The anti-adhesive layer may be, for example, a layer made of a silicone resin. It should be noted that the separation film 13 and the protective film 14 may also be composed only of a substrate film, and processing may be performed on the surface in contact with other layers in the substrate film to improve the peelability.
[0053] A half-cut process may be performed on a portion of the separation membrane 13. In other words, the separation membrane 13 has a cut extending from the surface of the separation membrane 13 to the middle of the separation membrane 13 in the thickness direction of the separation membrane 13. It should be noted that, in the separation membrane 13, the surface opposite to the surface in contact with the base membrane 11 is the surface.
[0054] like Figure 2As shown, the second example of the inspection patch 10 has an adhesive layer 15 in addition to the basement membrane 11, the separation membrane 13 and the protective film 14. In the second example of the inspection patch 10, the patch body 10B has the basement membrane 11 and the adhesive layer 15. The adhesive layer 15 is stacked on the basement membrane 11. The adhesive layer 15 is attached to the breast. In the patch body 10B, there are layers with functions of displaying indicators and layers with functions of being attached to the inspection object. Therefore, compared with the case where one layer has the function of displaying indicators and the function of being attached to the inspection object, the degree of freedom of the material used to form the inspection patch can be increased.
[0055] The adhesive layer 15 covers the back surface 11R of the base film. Therefore, by sandwiching the coordinate grid 12 between the base film 11 and the adhesive layer 15, the coordinate grid 12 does not constitute the outer surface of the inspection patch 10. As a result, the coordinate grid 12 is difficult to peel off from the base film 11. When viewed from the direction in which the adhesive layer 15 overlaps the base film 11, the adhesive layer 15 covers the entire base film 11. In the adhesive layer 15, the surface in contact with the base film 11 is the surface 15F, and the surface opposite to the surface 15F is the back surface 15R. The surface 15F of the adhesive layer 15 is in contact with the base film 11, and the back surface 15R of the adhesive layer 15 is in contact with the protective film 14.
[0056] The adhesive layer 15 covers the entire coordinate grid 12 and has a thickness such that the back surface 15R is substantially flat. In the inspection patch 10, the back surface 15R of the adhesive layer 15 is attached to the subject.
[0057] In the thickness direction of the base film 11, the patch body 10B is sandwiched between the separation film 13 and the protective film 14. Therefore, until just before the patch body 10B is attached to the subject, the patch body 10B is protected from the outside by the separation film 13 and the protective film 14. Thus, until it is attached to the subject, the patch body 10B is kept clean. The thickness of the adhesive layer 15 can be, for example, 5 μm or more and 25 μm or less.
[0058] The adhesive layer 15 is made of a synthetic resin similar to the base film 11. The synthetic resin used to form the adhesive layer 15 may be, for example, a polyurethane resin. By forming the adhesive layer 15 using a polyurethane resin, an adhesive layer 15 having a high moisture permeability can be obtained. In the patch body 10B, the adhesive layer 15 may be formed of a synthetic resin other than a polyurethane resin as long as the transmittance of the adhesive layer 15 to 2 GHz microwaves is 70% or more.
[0059] Below, refer to Figure 3 The coordinate grid 12 will be described in more detail.
[0060] like Figure 3As shown, the coordinate grid 12 includes a plurality of grid lines 12A. Each grid line 12A extends along a scanning direction DS, and the plurality of grid lines 12A are arranged along an arrangement direction DA perpendicular to the scanning direction DS. In the present embodiment, the left-right direction of the paper is the scanning direction DS. The scanning direction DS is the direction in which the inspector uses a probe to scan the inspection object. In addition, in the present embodiment, the arrangement direction DA is the up-down direction of the paper. In the arrangement direction DA, the first grid lines 12A1 having the first color and the second grid lines 12A2 having the second color are arranged alternately. The second color is different from the first color.
[0061] When the inspector uses the probe to scan along the scanning direction DS, the first grid line 12A1 and the second grid line 12A2 can be alternately scanned. This can prevent the inspector from scanning the same grid line 12A multiple times or from missing a grid line 12A. That is, scanning errors by the inspector can be reduced based on the grid lines 12A.
[0062] The first grid line 12A1 may be, for example, red, and the second grid line 12A2 may be, for example, blue. It should be noted that the first color as the color of the first grid line 12A1 and the second color as the color of the second grid line 12A2 are not limited to red and blue, and may be set arbitrarily as long as they are different colors.
[0063] The coordinate grid 12 also includes a plurality of grid lines 12B extending along the arrangement direction DA and arranged along the scanning direction DS. When viewed from a direction opposite to the plane in which the inspection patch 10 is unfolded, the plurality of grid lines 12B form a square grid together with the plurality of grid lines 12A. In each grid line 12B, the first division 12B1 and the second division 12B2 are arranged alternately. In the arrangement direction DA, each division area sandwiched by one first grid line 12A1 and one second grid line 12A2 adjacent to each other is divided into a first division 12B1 and a second division 12B2. Similar to the first grid line 12A1, the first division 12B1 has a first color. Similar to the second grid line 12A2, the second division 12B2 has a second color.
[0064] The coordinate grid 12 also includes a position mark 12C. In the present embodiment, the position mark 12C is a number used to mark the position in the coordinate grid 12. The position mark 12C includes, for example, a plurality of numbers arranged along the scanning direction DS. In the arrangement direction DA, the plurality of numbers are located outside the first grid line 12A1 at the upper end. In the scanning direction DS, each number is located between two grid lines 12B, or is located outside the grid line 12B at the edge. The position mark 12C includes, for example, a plurality of numbers arranged along the arrangement direction DA. In the scanning direction DS, the plurality of numbers are located outside the grid line 12B at the left end. In the arrangement direction DA, each number is located between two grid lines 12A. It should be noted that the position mark 12C is not limited to a plurality of numbers, and may include, for example, a plurality of characters.
[0065] Since the coordinate grid 12 includes the position markers 12C, the examiner can further improve the accuracy of the examination by referring to the position markers 12C. In addition, when a lesion is found in the breast, the position markers 12C can be used to calibrate the position of the lesion in the breast.
[0066] The coordinate grid 12 can be printed using ink on the back surface 11R of the base film 11. As the ink used for printing the coordinate grid 12, any ink that can be printed on the base film 11 can be used.
[0067] The inspection patch 10 also has a mark 16 indicating a predetermined position in the coordinate grid 12. In the present embodiment, the predetermined position is the central portion of the coordinate grid 12. The mark 16 is a circular point located in the central portion of the coordinate grid 12. The shape of the mark 16 is not limited to a circle and can be set arbitrarily. In addition, the mark 16 can also be composed of a plurality of parts separated from each other. In addition, as long as the mark 16 indicates the central portion of the coordinate grid 12, it can also be arranged at a position deviating from the central portion of the coordinate grid 12. Similar to the coordinate grid 12, the mark 16 can be printed on the back side 11R of the base film 11 using ink.
[0068] According to the mark 16, when using the inspection patch 10, the coordinates indicated by the mark 16 can be superimposed on a specific position of the breast. According to this embodiment, the subject can attach the inspection patch 10 to the breast so that the mark 16 is located at the nipple of the breast, so that the coordinate grid 12 can be located around the entire nipple. Thus, the inspection implementer can scan the entire breast along the circumferential direction of the nipple.
[0069] [How to use the inspection patch]
[0070] Reference Figures 4 to 6 , the method of using the inspection patch 10 is described. Figure 4The method of using the inspection patch 10 in the first example is described below. Figure 5 The method of using the inspection patch 10 in the second example will be described.
[0071] like Figure 4 As shown, when using the first example of the inspection patch 10, first, the user peels off the separation film 13 and the protective film 14 from the base film 11. When using the first example of the inspection patch 10, the separation film 13 can be peeled off before the protective film 14, or the protective film 14 can be peeled off before the separation film 13.
[0072] In addition, if Figure 5 As shown, when using the second example of the inspection patch 10, the user peels off the separation film 13 from the base film 11, and peels off the protective film 14 from the adhesive layer 15. It should be noted that, similarly to the first example of using the inspection patch 10, the separation film 13 can be peeled off before the protective film 14, or the protective film 14 can be peeled off before the separation film 13.
[0073] like Figure 6 As shown, the patch bodies 10A and 10B are attached to the breast B of the subject S. At this time, the inspection patch 10 can be attached to the breast B so that the mark 16 of the inspection patch 10 overlaps the nipple. In this embodiment, since the mark 16 is located in the center of the coordinate grid 12, by overlapping the mark 16 with the nipple, a part of the coordinate grid 12 can be located in the entire circumferential direction of the nipple. Thus, the entire breast B can be easily scanned under the guidance of the coordinate grid 12.
[0074] When the patch body 10A, 10B is attached to the breast B, the position of the mark 16 is overlapped with the position of the nipple while the four sides constituting the edge of the laminate are stretched outward. Then, by slowly attaching the laminate from the upper end of the patch body 10A, 10B to the breast B, wrinkles on the basement membrane 11 can be suppressed. It should be noted that, in the patch body 10A, 10B, the side located above the nipple is the upper end, and the side located below the nipple is the lower end. In the case where wrinkles are generated on the basement membrane 11, in the patch body 10A, 10B, the part of the basement membrane 11 including the wrinkled part can be peeled off from the breast B, and the patch body 10A, 10B is applied with a tensile force to pull the basement membrane 11 toward the outer side of the edge, and in this state, the patch body 10A, 10B is attached to the breast B. In this way, the wrinkles generated on the basement membrane 11 can be removed.
[0075] It should be noted that when attaching the patch body 10A, 10B to the breast B, a clamp capable of pulling the patch body 10A, 10B toward the outside of the edge of the patch body 10A, 10B may be used. In addition, as described above, in the case where the separation membrane 13 is half-cut, the patch body 10A, 10B may be attached to the breast B according to the following steps. That is, after the protective film 14 is peeled off from the patch body 10A, 10B, the laminated body of the separation membrane 13 and the patch body 10A, 10B is attached to the breast B. Then, the separation membrane 13 is peeled off from the base film 11.
[0076] As described above, in the present embodiment, the grid lines 12A extending along the scanning direction DS include the first grid lines 12A1 and the second grid lines 12A2 having different colors from each other, and in the arrangement direction DA, the first grid lines 12A1 and the second grid lines 12A2 are arranged alternately. Therefore, when the inspector uses the probe to scan along the scanning direction DS, the inspector can alternately scan along the first grid line 12A1 and along the second grid line 12A2. Thus, it is possible to prevent the inspector from scanning the same grid line 12A multiple times or from missing a grid line 12A. That is, according to the grid lines 12A, scanning errors of the inspector can be reduced.
[0077] [Test example]
[0078] Reference Figure 7 A test example will be described.
[0079] [Test Example 1-1]
[0080] As a test sheet of Test Example 1-1, an aluminum foil having a thickness of 7 μm (manufactured by UACJ Corporation, 1N30) was prepared.
[0081] [Test Example 1-2]
[0082] As the inspection patch of Test Example 1-2, two sheets of the aluminum foil used in Test Example 1-1 were stacked to prepare an aluminum foil having a thickness of 14 μm.
[0083] [Test Examples 1-3]
[0084] As the patch body, a polyvinylidene fluoride resin (Kynar FLEX2500, manufactured by Alkema Co., Ltd.) (Kynar is a registered trademark) was used to form a polyvinylidene fluoride resin (PVDF) film having a thickness of 80 μm by extrusion molding. Thus, the inspection patch of Test Example 1-3 was obtained.
[0085] [Test Examples 1-4]
[0086] Two PVDF films formed by the same molding method as in Test Example 1-3 were stacked to form a PVDF film having a thickness of 160 μm. Thus, the inspection patch of Test Example 1-4 was obtained.
[0087] [Test Example 1-5]
[0088] Four PVDF films formed by the same molding method as in Test Example 1-3 were stacked to form a PVDF film having a thickness of 320 μm. Thus, the inspection patch of Test Example 1-5 was obtained.
[0089] [Test Example 1-6]
[0090] As the inspection patch of Test Example 1-6, a 75 μm-thick ethylene-vinyl acetate copolymer resin (EVA) film (Midea, manufactured by Tatsuno Chemical Co., Ltd.) (Midea is a registered trademark) was prepared.
[0091] [Test Example 1-7]
[0092] Two EVA films used in Test Example 1-6 were stacked to form an EVA film having a thickness of 150 μm. Thus, the inspection patch of Test Example 1-7 was obtained.
[0093] [Test Example 1-8]
[0094] As the inspection patch of Test Example 1-8, an EVA film having a thickness of 250 μm (MIDEA, manufactured by Tatsuno Chemical Co., Ltd.) was prepared.
[0095] [Test Example 1-9]
[0096] As the inspection patch of Test Example 1-9, a biaxially oriented polypropylene resin (OPP) film (FOR-MP, manufactured by Futamura Chemical Co., Ltd.) having a thickness of 40 μm was prepared.
[0097] [Test Example 1-10]
[0098] Two OPP films used in Test Example 1-9 were stacked to form an OPP film having a thickness of 80 μm. Thus, the inspection patch of Test Example 1-10 was obtained.
[0099] [Test Example 1-11]
[0100] The three OPP films used in Test Example 1-9 were stacked to form an OPP film having a thickness of 120 μm. Thus, the inspection patch of Test Example 1-11 was obtained.
[0101] [Test Example 1-12]
[0102] A polyurethane (PU) film having a thickness of 15 μm was formed by melt casting using an aqueous urethane resin (Takelack WS-6021 manufactured by Mitsui Chemicals, Inc.) (Takelack is a registered trademark). Thus, inspection patches of Test Examples 1-12 were obtained.
[0103] [Test Example 1-13]
[0104] Two PU films formed by the same film forming method as in Test Example 1-12 were stacked to form a PU film having a thickness of 30 μm. Thus, the inspection patch of Test Example 1-13 was obtained.
[0105] [Test Example 1-14]
[0106] Four PU films formed by the same film forming method as in Test Example 1-12 were stacked to form a PU film having a thickness of 60 μm. Thus, the inspection patch of Test Example 1-14 was obtained.
[0107] [Test Example 1-15]
[0108] Six PU films formed by the same film-forming method as in Test Example 1-12 were stacked to form a PU film having a thickness of 90 μm. Thus, the inspection patch of Test Example 1-15 was obtained.
[0109] [Test Example 1-16]
[0110] Eight PU films formed by the same film-forming method as in Test Example 1-12 were stacked to form a PU film having a thickness of 120 μm. Thus, the inspection patch of Test Example 1-16 was obtained.
[0111] [Test Example 1-17]
[0112] As the inspection patch of Test Example 1-17, a polyethylene terephthalate resin (PET) film (manufactured by Toray Industries, Ltd., Lumira S10) (Lumira is a registered trademark) having a thickness of 12 μm was prepared.
[0113] [Test Example 1-18]
[0114] As the inspection patch of Test Example 1-18, a PET film having a thickness of 25 μm (manufactured by Toray Industries, Ltd., Lumira S10) was prepared.
[0115] [Test Example 1-19]
[0116] As the inspection patch of Test Example 1-19, a PET film having a thickness of 75 μm (manufactured by Toray Industries, Ltd., Lumira S10) was prepared.
[0117] [Test Example 1-20]
[0118] Two PET films used in Test Example 1-19 were stacked to form a PET film having a thickness of 150 μm. Thus, the inspection patch of Test Example 1-20 was obtained.
[0119] [Test Example 1-21]
[0120] As the inspection patch of Test Example 1-21, an elastic omentum with a thickness of 250 μm (manufactured by Meiwa Graphia Co., Ltd.) was prepared.
[0121] [Evaluation method]
[0122] [Determination of reference strength μ0]
[0123] A transmitter for oscillating 2 GHz microwaves and a receiver for receiving microwaves (Emuke Science & Technology Co., Ltd., DT-2G) were prepared. The intensity of the microwaves was measured for 30 seconds while the receiving part of the receiver was in contact with the transmitter. The maximum value measured within 30 seconds was taken as the intensity of the microwaves. The same measurement was performed three times, and the average value of each microwave intensity was calculated as the reference intensity μ0. The reference intensity μ0 was 1.85 mW / cm 2 .
[0124] [Measurement intensity μ m Determination of
[0125] The measurement intensity μ of each test example was measured by bringing the transmitter into contact with the receiving part of the receiver while the entire receiver (same as above) was covered with the inspection patch of each test example. m . Determination of intensity μ m The determination of is carried out by the same method as the reference intensity μ0.
[0126] [Evaluation results]
[0127] For each test example, the test patch was tested for strength μ m The measurement results are as follows Figure 7 shown.
[0128] [Evaluation results]
[0129] like Figure 7 As shown, it can be confirmed that the measured intensity μ of Test Example 1-1 m 0.00mW / cm 2 , Test Example 1-2 measured strength μ m 0.00mW / cm 2 , Test Example 1-3 measured strength μ m 1.43mW / cm 2In addition, it can be confirmed that the measured strength μ of Test Example 1-4 m 1.39mW / cm 2 , Test Examples 1-5 Measured Strength μ m 0.82mW / cm 2 , Test Examples 1-6 Measured Strength μ m 1.61mW / cm 2 In addition, it can be confirmed that the measured strength μ of Test Example 1-7 m 1.28mW / cm 2 , Test Examples 1-8 measured strength μ m 1.23mW / cm 2 , Test Example 1-9 measured strength μ m 1.54mW / cm 2 .
[0130] In addition, it can be confirmed that the measured strength μ of Test Example 1-10 m 1.36mW / cm 2 , Test Example 1-11 measured strength μ m 1.12mW / cm 2 , Test Example 1-12 measured strength μ m 1.71mW / cm 2 In addition, it can be confirmed that the measured strength μ of Test Example 1-13 m 1.67mW / cm 2 , Test Example 1-14 measured strength μ m 1.69mW / cm 2 , Test Example 1-15 measured strength μ m 1.37mW / cm 2 In addition, it can be confirmed that the measured strength μ of Test Example 1-16 m 1.18mW / cm 2 , Test Example 1-17 measured strength μ m 1.70mW / cm 2 , Test Example 1-18 measured strength μ m 1.68mW / cm 2 In addition, it can be confirmed that the measured strength μ of Test Example 1-19 m 1.46mW / cm 2 , Test Example 1-20 measured strength μ m 1.14mW / cm 2 , Test Example 1-21 measured strength μ m 1.32mW / cm 2 .
[0131] According to the reference strength μ0 and the measured strength μ of each test example m The microwave transmittance in each test case was calculated. The results are as follows: Figure 7 That is, Figure 7 As shown, it can be confirmed that the transmittance of Test Example 1-1 is 0%, the transmittance of Test Example 1-2 is 0%, and the transmittance of Test Example 1-3 is 78%. In addition, it can be confirmed that the transmittance of Test Example 1-4 is 75%, the transmittance of Test Example 1-5 is 44%, and the transmittance of Test Example 1-6 is 87%. In addition, it can be confirmed that the transmittance of Test Example 1-7 is 69%, the transmittance of Test Example 1-8 is 66%, and the transmittance of Test Example 1-9 is 84%.
[0132] In addition, it was confirmed that the transmittance of Test Example 1-10 was 74%, the transmittance of Test Example 1-11 was 61%, and the transmittance of Test Example 1-12 was 92%. In addition, it was confirmed that the transmittance of Test Example 1-13 was 91%, the transmittance of Test Example 1-14 was 92%, and the transmittance of Test Example 1-15 was 74%. In addition, it was confirmed that the transmittance of Test Example 1-16 was 64%, the transmittance of Test Example 1-17 was 92%, and the transmittance of Test Example 1-18 was 91%. In addition, it was confirmed that the transmittance of Test Example 1-19 was 79%, the transmittance of Test Example 1-20 was 62%, and the transmittance of Test Example 1-21 was 71%.
[0133] When scanning the breast using the probe through the inspection patch of each test example, it was confirmed whether a three-dimensional image capable of breast diagnosis can be generated. According to each inspection patch of Test Example 1-3, Test Example 1-4, Test Example 1-6, Test Example 1-9, Test Example 1-10, Test Example 1-12 to Test Example 1-15, Test Example 1-17 to Test Example 1-19, and Test Example 1-21, it can be confirmed that a three-dimensional image can be fully generated when attached to the subject. On the contrary, according to each inspection patch of Test Example 1-1, Test Example 1-2, Test Example 1-5, Test Example 1-7, Test Example 1-8, Test Example 1-11, Test Example 1-16, and Test Example 1-20, it can be confirmed that when attached to the subject, attenuation of microwaves occurs in the inspection patch, so that the transmittance is insufficient to generate a three-dimensional image.
[0134] From this, it was confirmed that a three-dimensional image that can be used for breast diagnosis can be formed by setting the microwave transmittance of the patch body in the inspection patch to 70% or more.
[0135] As described above, according to the first embodiment of the inspection patch, the advantages described below can be obtained.
[0136] (1-1) The inspector can be prompted to scan according to the indicators displayed on the patch body 10A, 10B, thereby improving the scanning accuracy of the inspection object. In addition, the patch body 10A, 10B has a transmittance of more than 70% with respect to microwaves with a frequency of 2 GHz, so the attenuation of microwaves caused by the oscillation of the probe can also be suppressed. As a result, the accuracy of the image obtained as the scanning result is improved, and as a result, the accuracy of the image diagnosis is improved.
[0137] (1-2) The state of the surface of the breast B can be grasped through the portion of the patch bodies 10A and 10B where the total light transmittance is 30% or more.
[0138] (1-3) Since the patch bodies 10A and 10B have the coordinate grid 12, no processing or tool is required for displaying indicators on the patch bodies 10A and 10B.
[0139] (1-4) According to the grid lines 12A, it is possible to reduce scanning errors by the inspector.
[0140] (1-5) When the inspection patch 10 is used, the coordinates indicated by the mark 16 can be superimposed on a specific position of the breast B.
[0141] (1-6) When the patch body 10B includes the base film 11 and the adhesive layer 15, the layer has a function of displaying an index and a layer of a function of attaching to the breast B. Therefore, compared with a case where a single layer has a function of displaying an index and a function of attaching to the breast B, the degree of freedom of the material used to form the inspection patch 10 can be increased.
[0142] [Modification of the first embodiment]
[0143] The first embodiment described above can be modified as follows.
[0144] [Patch body]
[0145] In the patch body 10A, 10B, the total light transmittance of the portion other than the coordinate grid 12 may be less than 30%. Even in this case, as long as the microwave transmittance of the patch body 10A, 10B is 70% or more, the advantage based on the above (1-1) can be obtained. In addition, the total light transmittance in the coordinate grid 12 may be 30% or more. In this case, the surface state of the breast B can be grasped through the coordinate grid 12.
[0146] The patch bodies 10A and 10B may not have indicators as exemplified by the coordinate grid 12. In this case, the indicators may be displayed on the patch bodies 10A and 10B by causing the patch bodies 10A and 10B to display various images projected by the projection device. Even in this case, the advantage based on the above (1-1) can be obtained.
[0147] The patch bodies 10A and 10B may have shapes other than a quadrilateral. The patch bodies 10A and 10B may have geometric shapes such as an ellipse, a circle, or a triangle, or may have an indefinite shape other than a geometric shape.
[0148] The patch body may have a multilayer structure consisting of three or more layers. Even in this case, as long as the patch body can display indicators and the transmittance of the patch body to 2 GHz microwaves is 70% or more, the advantage based on the above (1-1) can be obtained.
[0149] [Coordinate grid]
[0150] All grid lines 12A may also have the same color. Even in this case, the grid lines 12A can guide the direction of the probe scanning.
[0151] The coordinate grid 12 may have a shape other than a square grid. For example, the coordinate grid 12 may have a shape corresponding to polar coordinates formed by a plurality of concentric circles having different diameters from each other.
[0152] The coordinate grid 12 may not have the grid lines 12B. As long as the coordinate grid 12 has at least the grid lines 12A, scanning errors by the inspector can be prevented. That is, the basement membrane 11 is not limited to having the coordinate grid 12, and may have scanning indicators of other shapes such as a shape extending in one direction. The scanning indicators may be any scanning indicator as long as (for example) they can guide the position to be scanned by the probe or guide the scanning direction.
[0153] The coordinate grid 12 may not have the position marks 12C. As long as the coordinate grid 12 has at least the grid lines 12A, it is possible to prevent the inspector from making a scanning error.
[0154] The patch bodies 10A and 10B are not limited to the coordinate grid 12, and may have scanning indicators in the form of patterns extending in one direction, or indicators in the form of numbers or characters. The scanning indicators may indicate the position to be scanned or the scanning direction by a probe, for example.
[0155] The coordinate grid 12 may not be formed by printing. For example, the coordinate grid 12 may be formed by the concave portions and convex portions of the base film 11 .
[0156] [mark]
[0157] Even in this case, as long as the patch body 10A, 10B has the coordinate grid 12, the patch body 10A, 10B can be attached to the breast B by adjusting the position of the coordinate grid 12 relative to the breast B so that the entire circumference of the nipple can be scanned.
[0158] Similar to the coordinate grid 12 , the marks 16 may not be formed by printing. For example, the marks 16 may be formed by concave portions and convex portions of the base film 11 .
[0159] [Basement membrane]
[0160] The thickness of base film 11 may be greater than 30 μm or less than 5 μm. Even in this case, as long as the microwave transmittance in patch bodies 10A and 10B is 70% or more, the advantage based on the above (1-1) can be obtained.
[0161] The patch body 10A, i.e., the basement membrane 11, can be attached to the breast using, for example, an adhesive having adhesive properties. The adhesive can be, for example, an adhesive tape. In this case, in the basement membrane 11, the area further to the outside than the scanning index is attached to the breast by the adhesive. The adhesive can be located on the back surface 11R of the basement membrane 11, or on the surface 11F of the basement membrane 11. In the case where the adhesive is located on the surface 11F of the basement membrane, the adhesive can be in a shape and size extending from the basement membrane 11 to the outside of the basement membrane 11.
[0162] The patch body may also include a base film 11 and an adhesive layer for being laminated on the base film 11. In this case, the base film 11 and the adhesive layer are separate, and when the patch body is used, the adhesive layer is laminated on the base film 11. The adhesive layer only needs to be a layer that can position the base film 11 on the breast by adhering to the breast. The adhesive layer may be, for example, an adhesive layer formed by the above-mentioned adhesive. Alternatively, the adhesive layer may be, for example, a layer formed by an ointment-like aliphatic hydrocarbon. That is, the adhesive layer may be, for example, a layer formed by an aliphatic hydrocarbon having a creamy texture. Even in this case, as long as the patch body can display scanning indicators and the microwave transmittance in the patch body is 70% or more, the advantages based on the above-mentioned (1-1) can be obtained.
[0163] [Adhesive layer]
[0164] The adhesive for forming the adhesive layer 15 may be an adhesive other than the urethane adhesive. For example, the adhesive for forming the adhesive layer 15 may be an acrylic adhesive.
[0165] [Separation membrane]
[0166] The separation film 13 may be omitted in the inspection patch 10. Even in this case, the advantage based on the above (1-1) can be obtained as long as the patch bodies 10A and 10B can display indicators and the microwave transmittance in the patch bodies 10A and 10B is 70% or more.
[0167] [Protective film]
[0168] The protective film 14 may be omitted in the inspection patch 10. Even in this case, the advantage based on the above (1-1) can be obtained as long as the patch bodies 10A and 10B can display indicators and the microwave transmittance in the patch bodies 10A and 10B is 70% or more.
[0169] [Inspection object]
[0170] The inspection object is not limited to the breast, but may be other parts of the human body. That is, the inspection patch 10 is not limited to mammography, but may be used for other image diagnosis.
[0171] [Second embodiment]
[0172] Reference Figure 1 , Figure 4 ,as well as Figures 8 to 11 , the second embodiment of the inspection patch is described. For the components in the second embodiment that are common to the first embodiment, the symbols used in the first embodiment are given, thereby omitting the detailed description of the components. The inspection patch, the method of using the inspection patch, and the test examples are described in sequence below.
[0173] [Inspection patch]
[0174] Reference Figure 1 and Figure 8 , the inspection patch is described below. Figure 1 The configuration of the third example of the inspection patch is described below. Figure 8 The configuration of the fourth example of the inspection patch will be described.
[0175] It should be noted that, similar to the inspection patch of the first embodiment, the inspection patch of this embodiment is a patch used for mammography, which is an example of image diagnosis using microwaves. In mammography, the inspection patch is a patch attached to the breast to be inspected.
[0176] The third example of the inspection patch 10 has the same Figure 1 The structure is the same as the first example of the inspection patch 10 of the first embodiment described above. In this embodiment, the base film 11 satisfies the following two conditions.
[0177] (Condition 2-1) The tensile elongation at break is 130% or more.
[0178] (Condition 2-2) 100% tensile strength is 4 N / cm or less.
[0179] The inspection patch 10 has a tensile elongation at break and a modulus of 100% suitable for being attached to the inspection object. Therefore, the inspection patch 10 can be easily attached to the inspection object.
[0180] The tensile elongation at break can be determined according to JIS K 7161-1:2014 (ISO 527-1) and JIS K 7127:1999 (ISO 527-3). When the object to be measured has no yield point, the tensile strain at break can be measured, and when the object has a yield point, the nominal strain at tensile break can be measured, and the tensile elongation at break can be determined using these measured values.
[0181] The 100% tensile strength is a value obtained by dividing the force measured when the strain reaches a predetermined value (100%) defined in JIS K 7161-1:2014 (ISO 527-1) by the width of the test piece. The 100% tensile strength (T) (N / cm) can be obtained by the following formula.
[0182] T=F / W
[0183] In the above formula, F is the magnitude of the force to be measured (N), and W is the width of the test piece (cm).
[0184] The polyurethane resin used to form the base film 11 includes at least one selected from the group consisting of ether polyurethane resins, ester polyurethane resins, and carbonate polyurethane resins. Thus, the base film 11 having high lamination adaptability can be obtained.
[0185] Ether polyurethane resin refers to a polyurethane resin produced using an ether polyol containing an ether bond (-O-). Ester polyurethane resin refers to a polyurethane resin produced using an ester polyol containing an ester bond (-COO-). Carbonate polyurethane resin refers to a polyurethane resin produced using a polyol containing a carbonate bond (-OC(=O)O-). The thickness of the base film 11 can be, for example, not less than 5 μm and not more than 30 μm.
[0186] The base film 11 has a pair of surfaces facing each other. The pair of surfaces is composed of a surface 11F and a back surface 11R. In the present embodiment, the coordinate grid 12 is located on the back surface 11R. The base film 11 is transparent or translucent. In the portion of the base film 11 other than the coordinate grid 12, the total light transmittance specified in JIS K 7361-1 is more preferably 50% or more.
[0187] Similar to the inspection patch 10 of the first embodiment, the inspection patch 10 further includes a separation film 13 and a protective film 14. The separation film 13 is laminated on the surface 11F of the base film 11 in a peelable manner. The protective film 14 is laminated on the back surface 11R of the base film 11 in a peelable manner. In the portion of the inspection patch 10 other than the coordinate grid 12, the total light transmittance specified in JIS K7361-1 is preferably 30% or more, more preferably 50% or more.
[0188] The protective film 14 is transparent or translucent. The total light transmittance of the protective film 14 is preferably 30% or more, more preferably 50% or more.
[0189] like Figure 8 As shown in FIG. 1 , the fourth example of the inspection patch 10 further includes a fluidized layer 17 in addition to the basement membrane 11, the separation membrane 13, and the protective film 14. The fluidized layer 17 is formed of an aliphatic hydrocarbon that transmits microwaves more than water. The fluidized layer 17 has a viscosity that allows the basement membrane 11 to be attached to the breast, and is laminated on the basement membrane 11. That is, the microwave transmittance in the fluidized layer 17 is higher than the microwave transmittance in water. By providing the inspection patch 10 with the fluidized layer 17, the step of applying a drug on the inspection object for attaching the basement membrane 11 to the breast can be omitted, so that the basement membrane 11 can be attached to the breast more easily.
[0190] The fluidized layer 17 is formed of a paste-like aliphatic hydrocarbon. In the present embodiment, the fluidized layer 17 covers the back surface 11R of the base film 11. Therefore, by sandwiching the coordinate grid 12 between the base film 11 and the fluidized layer 17, the coordinate grid 12 does not constitute the outer surface of the inspection patch 10. As a result, the coordinate grid 12 is difficult to peel off from the base film 11.
[0191] In the thickness direction of the inspection patch 10, the fluidized layer 17 is located between the base film 11 and the protective film 14. In the fluidized layer 17, the surface in contact with the base film 11 is the surface 17F, and the surface opposite to the surface 17F is the back surface 17R. The fluidized layer 17 covers the entire coordinate grid 12 and has a thickness that makes the back surface 17R a substantially flat surface. The fluidized layer 17 is transparent or translucent.
[0192] In the fluidized bed 17, the shear viscosity at 30°C is preferably 1000 mPa·s to 200000 mPa·s. In the fluidized bed 17, the shear viscosity at 30°C is more preferably 5000 mPa·s to 50000 mPa·s. The shear viscosity is defined in JIS Z 8803:2011.
[0193] By setting the shear viscosity to 1000 mPa·s or more, the reliability of the fluidized layer 17 attaching the basement membrane 11 to the breast can be improved. On the other hand, by setting the shear viscosity to 200000 mPa·s or less, when the fluidized layer 17 is formed by coating on the basement membrane 11, wrinkles or loosening can be suppressed. Furthermore, by setting the shear viscosity to 200000 mPa·s or less, the discomfort caused to the subject by the stickiness of the fluidized layer 17 can be suppressed, and the difficulty in wiping the fluidized layer 17 can be suppressed.
[0194] The fluidized layer 17 is preferably composed of at least one selected from the group consisting of paraffin wax, squalane, and ceresin wax. These materials allow the fluidized layer 17 to reliably transmit microwaves and reduce irritation to the subject's skin.
[0195] [How to use the inspection patch]
[0196] Reference Figure 4 , Fig. 9 and Fig.10 , the method of using the inspection patch 10 is described. Figure 4 , the method of use of the inspection patch 10 in the third example is described, referring to Fig. 9 , the method of using the inspection patch 10 in the fourth example is described.
[0197] like Figure 4 As shown, when using the third example of the inspection patch 10, first, the user peels off the separation film 13 and the protective film 14 from the base film 11. When using the third example of the inspection patch 10, the separation film 13 can be peeled off before the protective film 14, or the protective film 14 can be peeled off before the separation film 13.
[0198] It should be noted that, in the case of the third example of using the inspection patch 10, an ointment-like aliphatic hydrocarbon having the same material as that constituting the fluidized layer 17 is applied to the breast of the subject. Then, the basement membrane 11 is attached to the breast via the ointment-like aliphatic hydrocarbon. In order to smoothly perform the inspection, it is preferred to apply the ointment-like aliphatic hydrocarbon to the breast before peeling off the separation film 13 and the protective film 14 from the basement membrane 11.
[0199] In addition, if Fig. 9As shown, when using the fourth example of the inspection patch 10, the user peels off the separation membrane 13 from the base membrane 11, and peels off the protective film 14 from the fluidized bed 17. It should be noted that, as in the first example of using the inspection patch 10, the separation membrane 13 may be peeled off before the protective film 14, or the protective film 14 may be peeled off before the separation membrane 13.
[0200] like Fig.10 As shown, whether the third example or the fourth example of the inspection patch 10 is used, the basement membrane 11 is attached to the breast B of the subject S via the aliphatic hydrocarbon H in an ointment form.
[0201] [Test example]
[0202] Reference Fig.11 , a test example of the inspection patch is described.
[0203] [Test Example 2-1]
[0204] As a base film of Test Example 2-1, a PET film (manufactured by Toray Industries, Ltd., Lumira S10) (Lumira is a registered trademark) having a thickness of 12 μm was prepared.
[0205] [Test Example 2-2]
[0206] As the base film of Test Example 2-2, a PET film having a thickness of 4.5 μm (manufactured by Toray Industries, Ltd., Lumira F48) was prepared.
[0207] [Test Example 2-3]
[0208] A PET film (manufactured by Toray (Strain), セラピール BX-9) (セラピー is a registered trademark) having a release layer and a thickness of 75 μm was prepared as a separation membrane. Then, by using the separation membrane as a support, an EVA resin (ethylene-vinyl acetate copolymer resin) (Nippon Polyethylene (Strain), Nobatch LV440) (Nobatch is a registered trademark) was extruded and laminated to form an EVA film with a thickness of 30 μm as a base membrane. Then, by peeling off the separation membrane, the base membrane of Test Example 2-3 was obtained.
[0209] [Test Example 2-4]
[0210] In Test Example 2-3, except that the thickness of the base film was changed to 15 μm, a base film of Test Example 2-4 was obtained by the same method as in Test Example 2-3.
[0211] [Test Example 2-5]
[0212] A base film of Test Example 2-5 was obtained by the same method as in Test Example 2-3 except that the thickness of the base film was changed to 5 μm.
[0213] [Test Example 2-6]
[0214] As a base film of Test Example 2-6, a PU film having a thickness of 30 μm and made of an ether-based polyurethane resin (ESMAR URS, manufactured by Nippon Matai Co., Ltd.) (ESMAR is a registered trademark) was prepared.
[0215] [Test Example 2-7]
[0216] As a base film of Test Example 2-7, a PU film having a thickness of 15 μm and made of an ether-based polyurethane resin (Silkron HVL85 manufactured by Okura Industries, Ltd.) (Silkron is a registered trademark) was prepared.
[0217] [Test Example 2-8]
[0218] As the base film of Test Example 2-8, a PU film (manufactured by Nakajima Industries, Ltd., thin-film urethane film) having a thickness of 5 μm was prepared.
[0219] [Test Example 2-9]
[0220] A water transfer tattoo patch (A-One transfer patch model: 52103 manufactured by Slide Em Japan Co., Ltd.) was prepared, and a PVA layer as an image receiving layer having a thickness of 5 μm was prepared as a base film of Test Example 2-9.
[0221] [Evaluation method]
[0222] [Tensile elongation at break]
[0223] According to the method of "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K 7127:1999, the inspection patch was cut into a dumbbell shape (test piece type 5), and for each test piece, the tensile elongation at break of each inspection patch was measured according to the method of JIS K7161-1:2014. In detail, the tensile elongation at break was measured by using a universal testing machine (manufactured by Shimadzu Corporation, Autograph AGS-X Roll Cell 1kN). The test piece was fixed at two locations by the fixed clamp of the universal testing machine, and the distance between the front ends of the fixed clamps at this time was set to 80mm. Then, the tensile speed was set to 300mm / min, and the test piece was stretched between the fixed positions of the test piece to obtain the elongation at break of the test piece.
[0224] [100% tensile strength]
[0225] According to the method of "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K 7127:1999, the inspection patch was cut into a dumbbell shape (test piece type 5), and for each test piece, the 100% tensile strength of each inspection patch was calculated according to the method of JIS K7161-1:2014. In detail, the 100% tensile strength was calculated using a universal testing machine (same as above). The test piece was fixed at two locations by the fixed clamps of the universal testing machine, and the distance between the front ends of the fixed clamps at this time was set to 80 mm. Then, the tensile speed was set to 300 mm / min, and the test piece was stretched between the fixed positions of the test piece. The measured force was divided by the width of the test piece to calculate the 100% tensile strength.
[0226] [Fit adaptability]
[0227] The adaptability of the inspection patch was evaluated using a breast cancer palpation training model (manufactured by Tanac Co., Ltd.). The basement membrane was formed of paraffin, and an ointment-like aliphatic hydrocarbon with a shear viscosity of 10,000 mPa·s at 30°C was attached to the breast of the model, and the following items were evaluated. It should be noted that the viscosity of the aliphatic hydrocarbon was measured by the following method. According to the "Viscosity measurement method using a single-cylinder rotational viscometer" in JIS Z 8803:2011, a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., equipped with a TVB-25L TM rotor 2) was used to measure the aliphatic hydrocarbons to be measured while maintaining the temperature at 30°C. It should be noted that the aliphatic hydrocarbons used were those after stirring for 1 minute.
[0228] (Item 1) Check for wrinkles on the patch
[0229] In item 1, when the basement membrane was attached to the breast, whether wrinkles were generated on the basement membrane was evaluated according to the following three levels. It should be noted that basement membranes evaluated as "○" or "△" in the following three levels are inspection patches with good adhesion adaptability.
[0230] ○: No wrinkles
[0231] △: Slight wrinkles are produced, but they do not affect the inspection
[0232] ×: Large wrinkles that may affect inspection are generated
[0233] [Evaluation results]
[0234] Reference Fig.11 , the results of each evaluation are explained.
[0235] like Fig.11As shown, it can be confirmed that if the base film is made of EVA resin, a base film with laminating adaptability can be obtained by making its thickness less than 15μm. In addition, it can be confirmed that if the base film is made of polyurethane resin, a base film with laminating adaptability can be obtained even if the thickness of the base film is 30μm. However, when the thickness of the base film is 30μm, although it does not affect the inspection, wrinkles will be generated on the base film, so the thickness of the base film made of polyurethane resin is preferably less than 30μm. In addition, it can be confirmed that even when a base film made of PVA resin is used, wrinkles will not be generated.
[0236] On the contrary, it can be confirmed that the lamination adaptability of the base film made of PET resin is low. Such a result can be said to be caused by the low tensile strength of the base film made of PET resin, which makes the base film unable to stretch when attached to the inspection object.
[0237] Therefore, the lamination adaptability can be improved according to the base film having a tensile elongation at break of 130% or more and a 100% modulus of 4 N / cm or less.
[0238] As described above, according to the second embodiment of the inspection patch, the following advantages can be obtained.
[0239] (2-1) The inspection patch 10 has a tensile elongation at break and a 100% modulus of strength suitable for being attached to the breast B. Therefore, the inspection patch 10 can be attached to the breast B easily.
[0240] (2-2) The base film 11 is formed of at least one of an ether-based polyurethane resin, an ester-based polyurethane resin, and a carbonate-based polyurethane resin. This can provide a base film 11 having high lamination suitability.
[0241] (2-3) When the inspection patch 10 includes the fluidized layer 17, the step of applying the drug on the breast B for attaching the basement membrane 11 to the breast B can be omitted, so that the basement membrane 11 can be attached to the breast B more easily.
[0242] (2-4) By setting the shear viscosity of the fluidized layer 17 to be 1000 mPa·s or more, the reliability of the fluidized layer 17 in attaching the basement membrane 11 to the breast B can be improved.
[0243] (2-5) By setting the shear viscosity of the fluidized layer 17 to 200,000 mPa·s or less, when the fluidized layer 17 is formed on the base film 11 by coating, it is possible to suppress the occurrence of wrinkles or sagging on the base film 11 .
[0244] (2-6) By forming the fluidized layer 17 from at least one of paraffin wax, squalene, and ceresin, the fluidized layer 17 can reliably transmit microwaves and reduce irritation to the subject's skin.
[0245] [Modification of the Second Embodiment]
[0246] It should be noted that the second embodiment described above may be modified as follows.
[0247] [Basement membrane]
[0248] As long as the base film 11 included in the inspection patch 10 satisfies the above conditions 2-1 and 2-2, the synthetic resin used to form the base film 11 may be a resin other than polyurethane resin. For example, as can be seen from the base film of the test example, the synthetic resin used to form the base film 11 may also be EVA resin or PVA resin.
[0249] [Flow layer]
[0250] The material for forming the fluidized layer 17 may be an ointment-like aliphatic hydrocarbon other than paraffin, squalane, and ceresin, as long as it transmits microwaves more than water and allows the basement membrane 11 to be attached to the breast B.
[0251] As long as the basement membrane 11 can be attached to the breast B through the fluidized layer 17, the viscosity of the fluidized layer 17 may be lower than 1000 mPa·s or higher than 200000 mPa·s.
[0252] [Separation membrane]
[0253] The separation film 13 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 satisfying the above conditions 2-1 and 2-2, the advantage based on the above (2-1) can be obtained.
[0254] [Protective film]
[0255] The protective film 14 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 satisfying the above conditions 2-1 and 2-2, the advantage based on the above (2-1) can be obtained.
[0256] [Inspection patch]
[0257] In the inspection patch 10, the total light transmittance only needs to be 50% or more in at least the portion of the base film 11 other than the coordinate grid 12. In this case, by peeling off the separation film 13 from the surface 11F of the base film 11 and peeling off the protective film 14 from the back surface 11R, the coordinate grid 12 of the base film 11 can be observed.
[0258] It should be noted that in the inspection patch 10, the total light transmittance in the portion other than the coordinate grid 12 in the laminate of the separation membrane 13 and the base membrane 11 can be 50% or more. Thus, when the inspection patch 10 is attached to the inspection object, the coordinate grid 12 of the base membrane 11 can be observed regardless of whether the separation membrane 13 is peeled off from the base membrane 11 or not.
[0259] [Third embodiment]
[0260] Reference Figure 2 , Fig.12 and Fig.13 , the third embodiment of the inspection patch is described. In the third embodiment, the configuration common to the inspection patch 10 of the first embodiment is given the same reference numerals as those used in the first embodiment, thereby omitting the detailed description of the configuration. The inspection patch and the test example are described in sequence below.
[0261] [Inspection patch]
[0262] Reference Figure 2 , the inspection patch is explained.
[0263] Similar to the inspection patch 10 of the first embodiment, the inspection patch of the present embodiment is a patch used for mammography, which is an example of image diagnosis using microwaves. In mammography, the inspection patch is a patch attached to the breast to be inspected.
[0264] The inspection patch 10 has the same Figure 2 The structure of the second example of the inspection patch 10 of the first embodiment described above is the same. In this embodiment, the base film 11 is formed of a polyurethane resin. The adhesive layer 15 is formed of a urethane adhesive. The adhesive layer 15 is laminated on the base film 11. The thickness of the adhesive layer 15 is not less than 5 μm and not more than 25 μm.
[0265] In the present embodiment, in the inspection patch 10 , the following three conditions are satisfied in the laminated body of the base film 11 and the adhesive layer 15 .
[0266] (Condition 3-1) The tensile elongation at break specified in JIS K 7127 is 130% or more.
[0267] (Condition 3-2) 100% modulus of elongation is 10 MPa or less.
[0268] (Condition 3-3) The moisture permeability specified in JIS Z 0208 is 750 g / m at 40°C and 90% relative humidity. 2 · More than one day.
[0269] The inspection patch 10 has a tensile elongation at break and a 100% modulus of tensile stress suitable for being attached to the inspection object. Therefore, the inspection patch 10 can be easily attached to the inspection object. In addition, by making the moisture permeability of the inspection patch 10 satisfy the above range, when the inspection patch 10 is attached to the inspection object, sweating of the inspection object can be suppressed.
[0270] The polyurethane resin used to form the base film 11 includes any one selected from the group consisting of ether polyurethane resins, ester polyurethane resins, and carbonate polyurethane resins. Thus, the base film 11 having high lamination suitability and high moisture permeability can be obtained.
[0271] Ether polyurethane resin refers to a polyurethane resin produced using an ether polyol containing an ether bond (-O-). Ester polyurethane resin refers to a polyurethane resin produced using an ester polyol containing an ester bond (-COO-). Carbonate polyurethane resin refers to a polyurethane resin produced using a polyol containing a carbonate bond (-OC(=O)O-).
[0272] When the base film 11 is formed of an ether polyurethane resin, the thickness of the base film 11 is preferably 30 μm or less. The thickness of the base film 11 may be, for example, 5 μm or more and 30 μm or less. When the base film 11 is formed of an ester polyurethane resin, the thickness of the base film 11 may be, for example, 5 μm or more and 15 μm or less. When the base film 11 is formed of a carbonate polyurethane resin, the thickness of the base film may be, for example, 5 μm or more and 15 μm or less.
[0273] The base film 11 has a pair of surfaces facing each other. The pair of surfaces is composed of a surface 11F and a back surface 11R. One of the pair of surfaces is a guide surface on which a coordinate grid 12 is printed. In the present embodiment, the coordinate grid 12 is located on the back surface 11R. That is, the back surface 11R is an example of a guide surface. The base film 11 is transparent or translucent. In the base film 11, the total light transmittance specified in JIS K7361-1 is preferably 30% or more, and more preferably 50% or more.
[0274] The adhesive layer 15 is transparent or translucent, and the total light transmittance of the adhesive layer 15 is preferably 50% or more.
[0275] The separation film 13 and the protection film 14 are preferably films made of a transparent or translucent synthetic resin.
[0276] [Test example]
[0277] Reference Fig.12 and Fig.13 , a test example of the inspection patch is described.
[0278] [Test Example 3-1]
[0279] A PET film (manufactured by Toray Co., Ltd., Lumira S10) (Lumira is a registered trademark) with a thickness of 12 μm was prepared as a base film. In addition, a protective film (manufactured by Toray Film Processing Co., Ltd., Celapil WZ) (Celapil is a registered trademark) with a thickness of 38 μm and composed of a PET film and a release layer was prepared. An acrylic adhesive (manufactured by Cosmed Pharmaceutical Co., Ltd., HiPAS10) (HiPAS is a registered trademark) was applied to the protective film using gravure coating, and the acrylic adhesive was dried. Thus, an adhesive layer with a thickness of 20 μm was obtained. Next, a laminate was obtained by pasting the base film and the adhesive layer together. The inspection patch of Test Example 3-1 was obtained by aging the laminate in an environment of 40°C.
[0280] [Test Example 3-2]
[0281] In Test Example 3-1, a test patch of Test Example 3-2 was obtained by the same method as in Test Example 3-1, except that the base film was changed to a PET film having a thickness of 4.5 μm (manufactured by Toray Industries, Ltd., Lumira F48).
[0282] [Test Example 3-3]
[0283] A PET film (manufactured by Toray, Celapil BX-9) with a release layer and a thickness of 75 μm was prepared as a separation membrane. Then, by using the separation membrane as a support, an EVA resin (Poly Etchlen, Nobatch LV440) (Nobatch is a registered trademark) was extruded and laminated to form an EVA film with a thickness of 30 μm as a base membrane. In addition, the inspection patch of Test Example 3-3 was obtained by the same method as Test Example 3-1. It should be noted that when the adhesive layer coated on the protective film is attached to the base membrane, the laminate of the separation membrane and the base membrane is attached to the adhesive layer. Then, after aging the laminate composed of the separation membrane, the base membrane, the adhesive layer and the protective film, the separation membrane is peeled off, thereby used as the inspection patch of Test Example 3-3.
[0284] [Test Example 3-4]
[0285] In Test Example 3-3, except that the thickness of the base film was changed to 15 μm, a test patch of Test Example 3-4 was obtained by the same method as in Test Example 3-3.
[0286] [Test Example 3-5]
[0287] In Test Example 3-3, except that the thickness of the base film was changed to 5 μm, a test patch of Test Example 3-5 was obtained by the same method as in Test Example 3-3.
[0288] [Test Example 3-6]
[0289] In Test Example 3-5, a urethane adhesive (Toyochem Co., Ltd., SP-205) was used to form the adhesive layer, and the inspection patch of Test Example 3-6 was obtained by the same method as in Test Example 3-5. It should be noted that when forming the adhesive layer, after adding 1% of a curing agent (Toyochem Co., Ltd., T-501B) to the urethane adhesive, the urethane adhesive was stirred to obtain a coating liquid for forming the adhesive layer.
[0290] [Test Example 3-7]
[0291] A test patch of Test Example 3-7 was obtained by the same method as in Test Example 3-1 except that the base film was changed to a 30 μm-thick PU film (ESMAR URS, manufactured by Nippon Matai Co., Ltd.) (ESMAR is a registered trademark).
[0292] [Test Example 3-8]
[0293] In Test Example 3-7, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-8 was obtained by the same method as in Test Example 3-7.
[0294] [Test Example 3-9]
[0295] In Test Example 3-7, except that the thickness of the adhesive layer was changed to 5 μm, a test patch of Test Example 3-9 was obtained by the same method as in Test Example 3-7.
[0296] [Test Example 3-10]
[0297] In Test Example 3-7, except that the thickness of the adhesive layer was changed to 30 μm, a test patch of Test Example 3-10 was obtained by the same method as in Test Example 3-7.
[0298] [Test Example 3-11]
[0299] A PU film (ESMAURS, manufactured by Nippon Matai Co., Ltd.) with a thickness of 30 μm and formed of an ether-based polyurethane resin was prepared as a base film. In addition, a protective film (CELAPIRE WZ, manufactured by Toray Film Processing Co., Ltd.) with a thickness of 30 μm and composed of a PET film and an anti-adhesive layer was prepared. 1% of a curing agent (T-501B, manufactured by Toraychem Co., Ltd.) was added to a urethane adhesive (SP-205, manufactured by Toraychem Co., Ltd.), and the two were stirred to prepare a coating solution. Next, the coating solution was applied to the protective film using gravure coating, and the urethane adhesive was dried. Thus, an adhesive layer with a thickness of 20 μm was obtained. Then, a laminate was obtained by pasting the base film and the adhesive layer together. The laminate was aged in an environment of 40° C. to obtain a test patch of Test Example 3-11.
[0300] [Test Example 3-12]
[0301] In Test Example 3-11, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-12 was obtained by the same method as in Test Example 3-11.
[0302] [Test Example 3-13]
[0303] In Test Example 3-11, except that the thickness of the adhesive layer was changed to 5 μm, a test patch of Test Example 3-13 was obtained by the same method as in Test Example 3-11.
[0304] [Test Example 3-14]
[0305] In Test Example 3-11, except that the thickness of the adhesive layer was changed to 30 μm, a test patch of Test Example 3-14 was obtained by the same method as in Test Example 3-11.
[0306] [Test Example 3-15]
[0307] In Test Example 3-1, the inspection patch of Test Example 3-15 was obtained by the same method as Test Example 3-1, except that the base film was changed to a PU film with a thickness of 15 μm and formed of an ether-based polyurethane resin (manufactured by Okura Industries, Ltd., Silcron HVL85) (Silcron is a registered trademark).
[0308] [Test Example 3-16]
[0309] In Test Example 3-11, a test patch of Test Example 3-16 was obtained by the same method as in Test Example 3-11, except that the base film was changed to a PU film having a thickness of 15 μm and formed of an ether-based polyurethane resin (Silklon HVL85 manufactured by Okura Industries, Ltd.).
[0310] [Test Example 3-17]
[0311] In Test Example 3-1, a test patch of Test Example 3-17 was obtained by the same method as in Test Example 3-1, except that the base film was changed to a 5-μm-thick PU film (manufactured by Nakajima Industries, Ltd., thin-film urethane film).
[0312] [Test Example 3-18]
[0313] In Test Example 3-17, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-18 was obtained by the same method as in Test Example 3-17.
[0314] [Test Example 3-19]
[0315] In Test Example 3-17, except that the thickness of the adhesive layer was changed to 5 μm, a test patch of Test Example 3-19 was obtained by the same method as in Test Example 3-17.
[0316] [Test Example 3-20]
[0317] In Test Example 3-17, except that the thickness of the adhesive layer was changed to 30 μm, a test patch of Test Example 3-20 was obtained by the same method as in Test Example 3-17.
[0318] [Test Example 3-21]
[0319] In Test Example 3-11, a test patch of Test Example 3-21 was obtained by the same method as in Test Example 3-11 except that the base film was changed to a 5 μm-thick PU film (manufactured by Nakajima Industries, Ltd., thin-film urethane film).
[0320] [Test Example 3-22]
[0321] In Test Example 3-21, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-22 was obtained by the same method as in Test Example 3-21.
[0322] [Test Example 3-23]
[0323] In Test Example 3-21, except that the thickness of the adhesive layer was changed to 5 μm, a test patch of Test Example 3-23 was obtained by the same method as in Test Example 3-21.
[0324] [Test Example 3-24]
[0325] In Test Example 3-21, except that the thickness of the adhesive layer was changed to 30 μm, a test patch of Test Example 3-24 was obtained by the same method as in Test Example 3-21.
[0326] [Test Example 3-25]
[0327] A water transfer tattoo patch (manufactured by Sleeve Em Japan, A-one transfer patch model: 52103) was prepared. Then, instead of the base film, the co-sealed adhesive layer was pasted on the PVA layer as the image receiving layer, thereby obtaining the inspection patch of Test Example 3-25. It should be noted that since the PVA layer is coated on the release paper, after the PVA layer and the adhesive layer are pasted together, the release paper is moistened with a paper towel soaked in water, so that the PVA layer is transferred to the adhesive layer. Thus, the PVA layer is peeled off from the release paper. Then, by placing the laminate including the PVA layer and the adhesive layer under an environment of 40°C for 2 hours, the surface of the PVA layer is fully dried, and the inspection patch of Test Example 3-25 is evaluated. In addition, when attaching the inspection patch of Test Example 3-25, the laminate of the release paper and the PVA layer was attached to the adhesive layer stacked on the separation film, and then the separation film of the adhesive layer was peeled off. Afterwards, the adhesive layer was attached to the object, and then, the release paper was moistened to peel off the release paper from the PVA layer. In this state, the lamination adaptability of the inspection patch of Test Example 3-25 was evaluated.
[0328] [Test Example 3-26]
[0329] A PET film (manufactured by Toray Co., Ltd., Celapil BX-9) with a release layer and a thickness of 75 μm was prepared as a separation membrane. Then, an aqueous polyurethane containing an ester polyol (manufactured by Mitsui Chemicals Co., Ltd., Takluck WS-5984) (Takluck is a registered trademark) was applied and dried. Next, a base film with a thickness of 15 μm was obtained by aging the dried layer at room temperature for 2 days. An adhesive layer was formed on the base film by the same method as in Test Example 3-6, thereby obtaining the inspection patch of Test Example 3-26.
[0330] [Test Example 3-27]
[0331] In Test Example 3-26, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-27 was obtained by the same method as in Test Example 3-26.
[0332] [Test Example 3-28]
[0333] In Test Example 3-26, except that the thickness of the base film was changed to 5 μm, a test patch of Test Example 3-28 was obtained by the same method as in Test Example 3-26.
[0334] [Test Example 3-29]
[0335] In Test Example 3-28, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-29 was obtained by the same method as in Test Example 3-28.
[0336] [Test Example 3-30]
[0337] In Test Example 3-26, except that the aqueous polyurethane containing an ester polyol was changed to an aqueous polyurethane containing an ether polyol (manufactured by Mitsui Chemicals, Inc., Taklack WS-6021), a test patch of Test Example 3-30 was obtained by the same method as in Test Example 3-26.
[0338] [Test Example 3-31]
[0339] In Test Example 3-30, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-31 was obtained by the same method as in Test Example 3-30.
[0340] [Test Example 3-32]
[0341] In Test Example 3-30, except that the thickness of the base film was changed to 5 μm, a test patch of Test Example 3-32 was obtained by the same method as in Test Example 3-30.
[0342] [Test Example 3-33]
[0343] In Test Example 3-30, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-33 was obtained by the same method as in Test Example 3-30.
[0344] [Test Example 3-34]
[0345] In Test Example 3-26, except that the aqueous polyurethane containing an ester polyol was changed to an aqueous polyurethane containing a carbonate polyol (manufactured by Mitsui Chemicals, Inc., Taklack WS-6110), a test patch of Test Example 3-34 was obtained by the same method as in Test Example 3-26.
[0346] [Test Example 3-35]
[0347] In Test Example 3-34, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-35 was obtained by the same method as in Test Example 3-34.
[0348] [Test Example 3-36]
[0349] In Test Example 3-34, except that the thickness of the base film was changed to 5 μm, a test patch of Test Example 3-34 was obtained by the same method as that of Test Example 3-34.
[0350] [Test Example 3-37]
[0351] In Test Example 3-36, except that the thickness of the adhesive layer was changed to 10 μm, a test patch of Test Example 3-37 was obtained by the same method as in Test Example 3-36.
[0352] [Evaluation method]
[0353] [Tensile elongation at break]
[0354] The tensile elongation at break was measured according to the method of "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K 7127. When measuring the tensile elongation at break, the inspection patch is demolded into a dumbbell shape (test piece type 5), and the tensile fracture measurement is performed using a tensile testing machine. The tensile speed is set to 300 mm / min, and the distance L0 between the markings is set to 25 mm. The elongation at break is measured to calculate the elongation at the break. It should be noted that in the tensile fracture measurement, the tensile fracture measurement is performed on a laminate consisting only of a base film and an adhesive layer.
[0355] [100% modulus of tensile stress]
[0356] In the tensile fracture measurement, the tensile force when the elongation of the inspection patch is 100% was divided by the initial value of the cross-sectional area of the inspection patch to calculate the stress when the distance L0 between marking lines reached 100% elongation.
[0357] [Fit adaptability]
[0358] The breast cancer palpation training model (manufactured by Tanac Co., Ltd.) was used to evaluate the fit of the inspection patch. The inspection patch was attached to the breast of the model and the following three items were evaluated.
[0359] (Item 1) Check for wrinkles on the patch
[0360] (Item 2) Inspection patch bulge
[0361] (Item 3) Repeatedly attaching and peeling off the inspection patch (reusability)
[0362] In item 1, when the inspection patch was attached to the breast, whether wrinkles were generated on the inspection patch was evaluated according to the following three levels. It should be noted that the inspection patch evaluated as "○" or "△" in the following three levels is an inspection patch with good adhesion adaptability.
[0363] ○: No wrinkles
[0364] △: Slight wrinkles are produced, but they do not affect the inspection
[0365] ×: Large wrinkles that may affect inspection are generated
[0366] In item 2, when the inspection patch was attached to the breast, whether a part of the inspection patch protruded from the breast was evaluated according to the following three levels. It should be noted that the inspection patch evaluated as "○" or "△" in the following three levels is an inspection patch with good adhesion adaptability.
[0367] ○: No bulge
[0368] △: The nipple is bumpy, but it does not affect the inspection.
[0369] ×: The examination patch protrudes significantly from the breast, thus affecting the examination
[0370] In item 3, after attaching the inspection patch to the breast, the inspection patch was temporarily peeled off from the breast, and then attached to the breast again, and the following three levels were evaluated.
[0371] ○: The inspection patch can be attached, peeled off, and attached again
[0372] △: When the inspection patch is peeled off, the inspection patch is deformed, but it can be attached and used again
[0373] ×: When the inspection patch peels off, the inspection patch is damaged, or the inspection patch cannot be attached again
[0374] [Moisture Permeability]
[0375] The moisture permeability of the inspection patch was measured according to the method of "Moisture permeability test method for moisture-proof packaging materials (cup method)" based on JIS Z 0208. When measuring the moisture permeability, calcium chloride (anhydrous) was weighed as a moisture absorbent. Next, the initial weight of the moisture permeable cup containing the moisture absorbent was measured using an electronic balance. Then, the inspection patch was placed in an environment of 40°C and 90% relative humidity for 2 hours, and the weight of the moisture permeable cup was measured. After that, the increase in the weight of the moisture permeable cup was calculated as the amount of water vapor permeation.
[0376] [Sweating Research]
[0377] A 5 cm square test piece was cut from the test patch. Then, the test piece was attached to the arms of three healthy subjects, and each subject was allowed to stay in a test room at 40°C and 20% relative humidity for 5 minutes in a quiet state. Then, the test piece was peeled off from each subject, and it was confirmed whether sweating occurred in the part of the subject's arm after the test piece was peeled off.
[0378] ○: No sweating was found in any of the subjects
[0379] ×: At least one examinee was found to be sweating
[0380] [Evaluation results]
[0381] Reference Fig.12 and Fig.13 , the results of each evaluation are explained.
[0382] like Fig.12 As shown, it can be confirmed that by using a polyurethane resin base film, wrinkles can be suppressed on the inspection patch, and the reusability of the inspection patch is improved. It should be noted that when the thickness of the base film is 30 μm, although there is no effect on the inspection, wrinkles are generated on the inspection patch, so the thickness of the polyurethane resin base film is preferably 30 μm or less. In addition, when the thickness of the base film is 5 μm, although there is no effect on the inspection, deformation of the inspection patch is found in the reusability test, so the thickness of the base film is preferably 5 μm or more.
[0383] In addition, it was confirmed that by using a base film with high lamination adaptability, the tensile elongation at break of the inspection patch can be 420% or more, and the 100% tensile stress can be 10MPa or less. Thus, the lamination adaptability of the inspection patch can be improved. Then, it was confirmed that by using a base film with high moisture permeability, the moisture permeability of the inspection patch can be 783g / m 2 · More than one day, thereby suppressing sweating.
[0384] On the contrary, it can be confirmed that the laminating adaptability of the base film made of PET resin is low. Such a result can be said to be caused by the low tensile elongation in the base film made of polyethylene terephthalate resin, and the base film cannot be stretched when the inspection patch is attached to the inspection object. In addition, in the base film made of EVA resin, the laminating adaptability of the base film can be improved by reducing the thickness to 5μm. However, the moisture permeability of the base film made of EVA resin is low, so it is possible to produce sweating to the extent that the inspection is affected in the part where the inspection patch is attached. In addition, it can be confirmed that according to the base film made of PVA resin, the base film will be damaged, so the reusability of the inspection patch is low. On the other hand, even in the case of using a base film made of PVA resin, wrinkles and bulges will not be generated, so in terms of improving the laminating adaptability, the tensile elongation at break only needs to be 130% or more.
[0385] It can be confirmed that as an adhesive for forming the adhesive layer, the moisture permeability of the urethane adhesive is higher than that of the acrylic adhesive. In addition, it can be confirmed that by using the urethane adhesive to form the adhesive layer, the moisture permeability of the inspection patch can be made 750 g / m 2 · days or more, thereby, sweating can be suppressed. It should be noted that by reducing the thickness of the adhesive layer, the moisture permeability of the inspection patch can be increased, thereby suppressing sweating. However, ridges will be generated on the inspection patch due to the unevenness of the nipple. In addition, even in the case of using a urethane adhesive to form the adhesive layer, when the thickness of the adhesive layer is 30μm, it is difficult to suppress the subject's sweating due to the low moisture permeability. In addition, when the thickness of the adhesive layer is too thick, the adhesive force of the adhesive layer is too strong, so when the inspection patch is peeled off, it will cause a burden on the subject, or the inspection patch will be damaged by combination with the basement membrane. From this aspect, the thickness of the adhesive layer is preferably not less than 5μm and not more than 25μm.
[0386] like Fig.13 As shown, it can be confirmed that the tensile elongation at break is different depending on the polyol constituting the polyurethane resin, and thus the test results of the lamination adaptability are different. It can be confirmed that the tensile elongation at break of the base film made of ester polyurethane resin or ether polyurethane resin is higher than that of the base film made of carbonate polyurethane resin, so it is not easy to produce wrinkles. In addition, it can be confirmed that even if the thickness of the base film made of carbonate polyurethane resin is small compared with the base film made of ester polyurethane resin or ether polyurethane resin, it is not easy to produce deformation in the reusability test. In addition, it can be confirmed that the moisture permeability of the base film made of ether polyurethane resin is higher than that of the base film made of ester polyurethane resin or carbonate polyurethane resin, so even if the thickness of the base film is large, it can also suppress the sweating of the subject.
[0387] As described above, it can be confirmed that by using a polyurethane resin substrate film with high lamination adaptability, the tensile elongation at break of the inspection patch can be 310% or more and the 100% tensile stress can be 10 MPa or less. Therefore, it can be confirmed that the lamination adaptability of the inspection patch can be improved. Then, it can be confirmed that by using a polyurethane resin substrate film with high moisture permeability, the moisture permeability of the inspection patch can be 752 g / m 2 · More than one day, thereby suppressing sweating.
[0388] As described above, according to the third embodiment of the inspection patch, the following advantages can be obtained.
[0389] (3-1) The inspection patch 10 has a tensile elongation at break and a 100% modulus of tensile stress suitable for being attached to the breast B. Therefore, the inspection patch 10 can be easily attached to the breast B. In addition, by making the moisture permeability of the inspection patch 10 satisfy the above range, when the inspection patch 10 is attached to the breast B, sweating of the breast B can be suppressed.
[0390] (3-2) By forming the base film 11 using an ether-based polyurethane resin, an ester-based polyurethane resin, or a carbonate-based polyurethane resin, a base film 11 having high lamination suitability and high moisture permeability can be obtained.
[0391] [Variation of the third embodiment]
[0392] It should be noted that the third embodiment described above may be modified as follows.
[0393] [Basement membrane]
[0394] As long as the laminate of the base film 11 and the adhesive layer 15 included in the inspection patch 10 satisfies the above-mentioned conditions 3-1 to 3-3, the synthetic resin used to form the base film 11 may be a resin other than the polyurethane resin.
[0395] [Adhesive layer]
[0396] As long as the laminate of the base film 11 and the adhesive layer 15 included in the inspection patch 10 satisfies the above-mentioned conditions 3-1 to 3-3, the adhesive used to form the adhesive layer 15 may be an adhesive other than the urethane adhesive.
[0397] [Separation membrane]
[0398] The separation film 13 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 and the adhesive layer 15, the advantage based on the above-mentioned (3-1) can be obtained.
[0399] [Protective film]
[0400] The protective film 14 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 and the adhesive layer 15, the advantage based on the above-mentioned (3-1) can be obtained.
[0401] [Inspection patch]
[0402] In the inspection patch 10, the total light transmittance only needs to be 50% or more in at least the portion of the laminate of the base film 11 and the adhesive layer 15 excluding the coordinate grid 12. In this case, by peeling off the separation film 13 from the base film 11 and peeling off the protective film 14 from the adhesive layer 15, the coordinate grid 12 of the base film 11 can be observed.
[0403] It should be noted that in the inspection patch 10, the total light transmittance in the portion other than the coordinate grid 12 in the laminate of the separation film 13, the base film 11, and the adhesive layer 15 can be 50% or more. Thus, when the inspection patch 10 is attached to the inspection object, the coordinate grid 12 of the base film 11 can be observed regardless of whether the separation film 13 is peeled off from the base film 11 or not.
[0404] [Fourth embodiment]
[0405] Reference Figure 2 and Figures 14 to 17 , a fourth embodiment of the inspection patch is described. In the fourth embodiment, for the common configurations with the inspection patch 10 of the first embodiment, the symbols used in the first embodiment are given, thereby omitting the detailed description of the configurations. The inspection patch, the manufacturing method of the inspection patch, and the test examples are described in sequence below.
[0406] [Inspection patch]
[0407] Reference Figure 2 , the inspection patch is explained.
[0408] Similar to the inspection patch 10 of the first embodiment, the inspection patch of the present embodiment is a patch used for mammography, which is an example of image diagnosis using microwaves. In mammography, the inspection patch is a patch attached to the breast to be inspected.
[0409] The inspection patch 10 has the same Figure 2The structure is the same as the second example in the inspection patch 10 of the first embodiment described. It is provided with a base film 11 and an adhesive layer 15. The base film 11 has a coordinate grid 12 for guiding the scanning position in the inspection object. The coordinate grid 12 is an example of a scanning index. The adhesive layer 15 is stacked on the base film 11. The base film 11 includes a back surface 11R as a surface in contact with the adhesive layer 15, and a surface 11F as a surface on the opposite side of the back surface 11R. The surface 11F is the surface of the inspection object that is scanned by the probe during the inspection.
[0410] In the present embodiment, surface 11F of base film 11 satisfies the following two conditions.
[0411] (Condition 4-1) The arithmetic mean roughness Ra specified in JIS B 0601:2013 is 0.1 μm or more.
[0412] (Condition 4-2) The dynamic friction coefficient between the surface 11F and the metal surface is 3 or less as defined in JIS K 7125:1999.
[0413] Since the arithmetic mean roughness Ra on the surface 11F of the base film 11 is 0.1 μm or more, and the dynamic friction coefficient between the surface 11F of the base film 11 and the metal surface is 3 or less, when the probe is used to scan the surface 11F of the base film 11, the probe can be easily slid relative to the surface 11F. Thus, the probe can be smoothly scanned relative to the surface 11F of the base film 11.
[0414] The inspection patch 10 further includes a separation film 13. The separation film 13 has a coating surface formed of a polypropylene resin or a polyethylene resin. The surface 11F of the base film 11 is a surface in contact with the coating surface and has a shape following the coating surface.
[0415] The coated surface of the separation membrane 13 preferably satisfies the following conditions.
[0416] (Condition 4-3) On the coated surface, the arithmetic mean roughness Ra specified in JIS B 0601:2013 is 0.2 μm or more.
[0417] When the base film 11 is formed by applying the coating liquid for forming the base film 11 onto the coated surface of the separation membrane 13, the arithmetic mean roughness Ra on the surface 11F of the base film 11 tends to be smaller than the arithmetic mean roughness Ra on the coated surface of the separation membrane 13. In addition, the larger the arithmetic mean roughness Ra on the coated surface of the separation membrane 13, the larger the arithmetic mean roughness Ra on the surface 11F of the base film 11 tends to be.
[0418] As described above, the arithmetic mean roughness Ra on the coated surface of the separation membrane 13 is 0.2 μm or more. Therefore, when the base film 11 is formed by applying the coating liquid for forming the base film 11 on the coated surface, the reliability of making the arithmetic mean roughness Ra on the surface 11F of the base film 11 to be 0.1 μm or more can be improved. Thus, the patch 10 for inspection including the base film 11 can be obtained, wherein the base film 11 has the surface 11F that can improve the smoothness of the probe scanning.
[0419] In addition, the peel strength of the separation membrane 13 with respect to the base film 11 preferably satisfies the following conditions.
[0420] (Condition 4-4) The peel strength specified in JIS Z 0237:2009 is 0.3 N / 25 mm or less.
[0421] By making the peel strength less than 0.3N / 25mm, it is possible to prevent the separation membrane 13 from being difficult to peel off from the base membrane 11. Thereby, the operability of the inspection patch 10 can be improved. It should be noted that, the larger the arithmetic mean roughness Ra at at least one surface in the interface of the two layers, the greater the peel strength between the two layers tends to become. In addition, the larger the arithmetic mean roughness Ra at at least one surface in the interface of the two layers, the higher the adhesion between the two layers tends to become. According to this embodiment, by making the arithmetic mean roughness Ra on the surface 11F of the base membrane 11 more than 0.1μm, and making the peel strength of the separation membrane 13 relative to the base membrane 11 less than 0.3N / 25mm, the smoothness of the probe scanning and the operability of the inspection patch 10 can be improved at the same time.
[0422] In surface 11F of base film 11 , it is preferable that the following conditions are further satisfied.
[0423] (Condition 4-5) The arithmetic mean roughness Ra specified in JIS B 0601:2013 is less than 5 μm.
[0424] By setting the arithmetic mean roughness Ra on the surface 11F of the base film 11 to be less than 5 μm, the reliability of setting the peel strength of the separation membrane 13 with respect to the base film 11 to be 0.3 N / 25 mm or less can be improved.
[0425] The coated surface of the separation membrane 13 preferably further satisfies the following conditions.
[0426] (Condition 4-6) The arithmetic mean roughness Ra specified in JIS B 0601:2013 is less than 7 μm.
[0427] The arithmetic mean roughness Ra on the coated surface of the separation membrane 13 is less than 7 μm, so when the base film 11 is formed by applying the coating liquid for forming the base film 11 on the coated surface, the reliability of making the arithmetic mean roughness Ra on the surface 11F of the base film 11 less than 5 μm can be improved. As a result, it is difficult for the separation membrane 13 to peel off from the base film 11.
[0428] The synthetic resin used to form the base film 11 may be, for example, a polyurethane resin. The polyurethane resin may include at least one selected from the group consisting of an ether polyurethane resin, an ester polyurethane resin, and a carbonate polyurethane resin. Thus, a base film 11 having high lamination adaptability and high moisture permeability can be obtained.
[0429] Ether polyurethane resin refers to a polyurethane resin generated using an ether polyol containing an ether bond (-O-). Ester polyurethane resin refers to a polyurethane resin generated using an ester polyol containing an ester bond (-COO-). Carbonate polyurethane resin refers to a polyurethane resin generated using a polyol containing a carbonate bond (-OC(=O)O-). The thickness of the base film 11 can be, for example, not less than 5 μm and not more than 30 μm.
[0430] The base film 11 is transparent or translucent. In the base film 11, the total light transmittance specified in JIS K 7361-1 is preferably 30% or more, more preferably 50% or more.
[0431] The adhesive layer 15 is transparent or translucent. The total light transmittance of the adhesive layer 15 is preferably 30% or more, and more preferably 50% or more.
[0432] The adhesive used to form the adhesive layer 15 may be, for example, a urethane adhesive. By using a urethane adhesive to form the adhesive layer 15, an adhesive layer 15 having high moisture permeability can be obtained. The thickness of the adhesive layer may be, for example, 5 μm to 25 μm.
[0433] In the portion of the inspection patch 10 excluding the coordinate grid 12 , the total light transmittance specified in JIS K7361-1 is preferably 30% or more, and more preferably 50% or more.
[0434] The separation film 13 and the protection film 14 are preferably films made of a transparent or translucent synthetic resin.
[0435] [Method for manufacturing inspection patch]
[0436] Reference Figures 14 to 16 , a method for manufacturing the inspection patch 10 is described.
[0437] like Fig.14As shown, when manufacturing the inspection patch 10, first, the separation membrane 13 is prepared. As described above, the separation membrane 13 is preferably prepared such that the arithmetic mean roughness Ra of the coating surface 13R to be coated with the coating liquid is 0.2 μm or more and less than 7 μm.
[0438] When the inspection patch 10 is used, the separation film 13 is peeled off from the base film 11. Therefore, the material forming the base film 11 and the material forming the separation film 13, especially the material forming the coated surface 13R, are materials that can be peeled off from each other. For example, the material forming the base film 11 is polyurethane resin, and the material forming the coated surface 13R is preferably polypropylene resin or polyethylene resin.
[0439] However, when the coating liquid for forming the separation membrane 13 is applied to the coated surface 13R of the base film 11, it is preferred that the coated surface 13R has high wettability to the coating liquid. Thus, the thickness of the base film 11 can be suppressed from varying over the entire coated surface 13R. From this perspective, as described above, since the arithmetic mean roughness Ra on the coated surface 13R is 0.2 μm or more, the wettability of the coated surface 13R to the coating liquid can also be improved.
[0440] like Fig.15 As shown, a coating liquid for forming the base film 11 is applied to the coated surface 13R. Then, the base film 11 is formed by drying the coating liquid. At this time, since the coated surface 13R has sufficient wettability to the coating liquid, the coating liquid for forming the base film 11 is dried in a state following the unevenness of the coated surface 13R. As a result, the surface 11F of the base film 11 becomes a surface having unevenness following the unevenness of the coated surface 13R.
[0441] like Fig.16 As shown, the coordinate grid 12 and the mark 16 are printed on the back side 11R of the base film 11. It should be noted that, among the pigments used for printing the coordinate grid 12 and the mark 16, it is preferred to use pigments that meet the cosmetic standards stipulated in the "Law on Ensuring the Quality, Effectiveness and Safety of Pharmaceuticals, Medical Devices, etc." (Pharmaceutical Affairs Law). In addition, the solvent or dispersion medium of the pigment preferably does not contain toluene.
[0442] Next, by bonding the adhesive layer 15 formed on the protective film 14 and the base film 11 together, the previously described Figure 2 The test patch 10 described above. It should be noted that, among the adhesives used to form the adhesive layer 15, it is preferable to use an adhesive satisfying the biocompatibility specified in ISO10993.
[0443] [Test example]
[0444] Reference Fig.17, a test example of the inspection patch is described.
[0445] [Test Example 4-1]
[0446] A biaxially stretched polypropylene (OPP) film (manufactured by Futamura Chemical Co., Ltd., FOS) was prepared as a separation membrane. Then, an aqueous polyurethane containing an ether polyol (manufactured by Mitsui Chemical Co., Ltd., Takluck WS-6021) (Takluck is a registered trademark) was applied and the aqueous polyurethane was dried. Next, a base film with a thickness of 15 μm was obtained by aging the dried layer at room temperature for 2 days. Thus, the inspection patch of Test Example 4-1 was obtained.
[0447] [Test Example 4-2]
[0448] A biaxially stretched polypropylene (OPP) film (manufactured by Futamura Chemical Co., Ltd., FOR-MP) having one matte surface in a pair of surfaces was prepared. Then, the non-matte surface on the opposite side to the matte surface was subjected to sandblasting to form minute concave-convex surfaces on the surface of the non-matte surface. Next, a base film was formed on the non-matte surface by the same method as in Test Example 4-1. Thus, the inspection patch of Test Example 4-2 was obtained.
[0449] [Test Example 4-3]
[0450] A polypropylene (PP) laminated release paper (manufactured by Lintech Co., Ltd., EV130TPSG) was prepared as a separation membrane. Then, a base film was formed on one surface of the separation membrane by the same method as in Test Example 4-1. Thus, the inspection patch of Test Example 4-3 was obtained.
[0451] [Test Example 4-4]
[0452] A polypropylene (PP) laminated release paper (manufactured by Lintech, EV130TPD) was prepared as a separation membrane. Then, a base film was formed on one surface of the separation membrane by the same method as in Test Example 4-1. Thus, the inspection patch of Test Example 4-4 was obtained.
[0453] [Test example 4-5]
[0454] A test patch of Test Example 4-5 was obtained by the same method as in Test Example 4-4 except that the aqueous polyurethane containing an ether polyol was changed to an aqueous polyurethane containing an ether polyol (Mitsui Chemicals, Inc., Takluck W-5661).
[0455] [Test Examples 4-6]
[0456] A test patch of Test Example 4-6 was obtained by the same method as in Test Example 4-4 except that the aqueous polyurethane containing an ether polyol was changed to an aqueous polyurethane containing a carbonate polyol (Mitsui Chemicals, Inc., Takluck W-6110).
[0457] [Test Example 4-7]
[0458] A test patch of Test Example 4-7 was obtained by the same method as in Test Example 4-3 except that the separation membrane was changed to a polypropylene (PP) laminated release paper (LINTEC CORPORATION, EV130TPD FN-L).
[0459] [Evaluation method]
[0460] [Arithmetic mean roughness Ra]
[0461] The arithmetic mean roughness Ra was measured using a surface roughness / profile measuring instrument (Tokyo Seimitsu Co., Ltd., Subcom 130A) (Subcom is a registered trademark) in accordance with the method of JIS B 0601:2013 "Geometrical Specifications for Products (GPS) - Surface Texture: Profile Method - Terms, Definitions and Surface Texture Parameters".
[0462] [Dynamic friction coefficient]
[0463] The dynamic friction coefficient of the surface of the base film was measured according to the method of "Plastics - Film and Sheeting - Friction Coefficient Test Method" of JIS K 7125: 1999. The dynamic friction coefficient was measured using a friction coefficient meter (Toyo Seiki Seisaku-sho, TR-2).
[0464] When measuring the dynamic friction coefficient, an aluminum plate was placed on a smooth glass plate, and a basement membrane was attached to the aluminum plate so as to contact the back of each basement membrane. Then, an aluminum plate with a load of 200 g was prepared as a weight. Next, the weight was slid at a speed of 100 mm / min while the surface of the basement membrane was in contact with the weight to measure the magnitude of the friction force, and the dynamic friction coefficient was calculated when the weight was slid only 40 mm.
[0465] [Peel strength]
[0466] The peel strength of the separation membrane relative to the base membrane was measured according to the method of "Adhesive Tape / Adhesive Sheet Test Method" of JIS Z 0237:2009. In the determination of the peel strength, a desktop precision universal testing machine ((Strain) Shimadzu Manufacturing, AGS-X 5kN) was used. When measuring the peel strength, a test piece with a width of 25 mm was cut from each inspection patch. Then, the separation membrane was fixed on the desktop precision universal testing machine, and the strength when the base membrane was peeled 180° relative to the separation membrane was calculated.
[0467] [Evaluation results]
[0468] Reference Fig.17 , the results of each evaluation are explained. Fig.17 Here, the arithmetic mean roughness Ra of the base film refers to the arithmetic mean roughness Ra on the surface of the base film. On the other hand, the arithmetic mean roughness Ra of the separation membrane refers to the arithmetic mean roughness Ra on the coated surface of the separation membrane.
[0469] like Fig.17 As shown, it can be confirmed that the larger the arithmetic mean roughness Ra on the coated surface of the separation membrane is, the larger the arithmetic mean roughness Ra on the surface of the base film tends to be. In addition, it can be confirmed that in the inspection patch of Test Example 4-1, the arithmetic mean roughness Ra on the surface of the base film is less than 0.1, and the dynamic friction coefficient exceeds 3. In addition, it can be confirmed that in the inspection patch of Test Example 4-1, when the probe is scanned along the surface of the base film, the probe can be felt to be stuck on the surface of the base film.
[0470] On the contrary, it was confirmed that in the inspection patches of Test Examples 4-2 to 4-7, the arithmetic mean roughness Ra on the surface of the base film was greater than or equal to 0.1, and the dynamic friction coefficient was less than or equal to 3. In addition, it was confirmed that in the inspection patches of Test Examples 4-2 to 4-7, when the probe was scanned along the surface of the base film, no sticking of the probe to the surface of the base film was felt.
[0471] It should be noted that it can be confirmed that in the inspection patch of Test Example 4-7, since the dynamic friction coefficient is less than 3.0, when the probe is scanned along the surface of the base film, no jamming of the probe against the surface of the base film is felt. However, it can be confirmed that in the inspection patch of Test Example 4-7, since the peel strength exceeds 0.3N / 25mm, a large force is required to peel the separation membrane from the base film, and the operability of the inspection patch is reduced.
[0472] On the contrary, it was confirmed that in the test patches of Test Examples 4-2 to 4-6, since the peel strength was 0.3 N / 25 mm or less, it was not difficult to peel the separation membrane from the base membrane.
[0473] As described above, in order to make the probe scanning along the surface of the base film smooth, the arithmetic mean roughness Ra on the surface of the base film is preferably 0.1 μm or more, and the dynamic friction coefficient is preferably 3.0 or less. In this case, if the arithmetic mean roughness Ra of the coated surface of the separation membrane relative to the surface of the base film is 0.3 μm or more, the arithmetic mean roughness Ra on the surface of the base film can be made 0.2 μm or more.
[0474] In order to improve the operability of the test patch, the arithmetic mean roughness Ra of the surface of the base film is preferably less than 5.0. In this case, the arithmetic mean roughness Ra of the coated surface of the separation membrane relative to the surface of the base film is preferably less than 7.0 μm.
[0475] In summary, according to the fourth embodiment of the inspection patch, the following advantages can be obtained.
[0476] (4-1) When the probe is used to scan the surface 11F of the base film 11, the probe can be easily slid relative to the surface. Thus, the probe can smoothly scan the surface 11F of the base film 11.
[0477] (4-2) Since the arithmetic mean roughness Ra on the coated surface 13R of the separation membrane 13 is 0.2 μm or more, the reliability of making the arithmetic mean roughness Ra on the surface 11F of the base film 11 0.1 μm or more can be improved.
[0478] (4-3) By setting the peel strength to 0.3 N / 25 mm or less, it is possible to prevent the separation film 13 from being easily peeled off from the base film 11. This can improve the handleability of the inspection patch 10.
[0479] (4-4) By setting the arithmetic mean roughness Ra on the surface 11F of the base film 11 to be less than 5 μm, the reliability of setting the peel strength of the separation membrane 13 with respect to the base film 11 to be 0.3 N / 25 mm or less can be improved.
[0480] (4-5) Since the arithmetic mean roughness Ra of the coated surface 13R of the separation membrane 13 is less than 7 μm, the reliability of making the arithmetic mean roughness Ra of the surface 11F of the base membrane 11 less than 5 μm can be improved. Thus, the separation membrane 13 can be prevented from being easily peeled off from the base membrane 11.
[0481] [Variation of the Fourth Embodiment]
[0482] It should be noted that the fourth embodiment described above may be modified as follows.
[0483] [Basement membrane]
[0484] As long as the base film 11 included in the inspection patch 10 satisfies the above-mentioned conditions 4-1 and 4-2, the synthetic resin used to form the base film 11 may be a resin other than the polyurethane resin.
[0485] The base film 11 is not limited to being formed by applying the coating liquid to the coating surface 13R of the separation membrane 13 , and may be formed by an extrusion lamination method on the coating surface 13R of the separation membrane 13 .
[0486] The arithmetic mean roughness Ra of surface 11F of base film 11 may be 5 μm or more. Even in this case, as long as base film 11 satisfies conditions 4-1 and 4-2, the advantage based on (4-1) can be obtained.
[0487] [Adhesive layer]
[0488] The adhesive for forming the adhesive layer 15 may be an adhesive other than the urethane adhesive.
[0489] [Separation membrane]
[0490] The separation film 13 may be omitted. Even in this case, as long as the base film 11 satisfies the conditions 4-1 and 4-2, the advantage based on the above-mentioned (4-1) can be obtained.
[0491] As long as the base film 11 satisfies the above conditions 4-1 and 4-2, the arithmetic mean roughness Ra on the coated surface 13R of the separation membrane 13 may be less than 0.2 μm. Even in this case, the advantage based on the above (4-1) can be obtained.
[0492] The arithmetic mean roughness Ra on the coated surface 13R of the separation membrane 13 may be 7 μm or more. Even in this case, as long as the base film 11 satisfies the above conditions 4-5, the advantage based on the above (4-4) can be obtained.
[0493] [Protective film]
[0494] Protective film 14 may be omitted. Even in this case, as long as base film 11 satisfies conditions 4-1 and 4-2, the advantage based on (4-1) described above can be obtained.
[0495] [Inspection patch]
[0496] The peel strength of the separation film 13 with respect to the base film 11 may be greater than 0.3 N / 25 mm. Even in this case, as long as the base film 11 satisfies the above conditions 4-1 and 4-2, the advantage based on the above (4-1) can be obtained.
[0497] In the inspection patch 10, the total light transmittance only needs to be 50% or more in at least the portion of the laminate of the base film 11 and the adhesive layer 15 excluding the coordinate grid 12. In this case, by peeling off the separation film 13 from the base film 11 and peeling off the protective film 14 from the adhesive layer 15, the coordinate grid 12 of the base film 11 can be observed.
[0498] It should be noted that in the inspection patch 10, the total light transmittance in the portion other than the coordinate grid 12 in the laminate of the separation film 13, the base film 11, and the adhesive layer 15 can be 50% or more. Thus, when the inspection patch 10 is attached to the inspection object, the coordinate grid 12 of the base film 11 can be observed regardless of whether the separation film 13 is peeled off from the base film 11 or not.
[0499] [Fifth embodiment]
[0500] Reference Figure 2 and Fig.18 , the fifth embodiment of the inspection patch is described. In the fifth embodiment, the configuration common to the inspection patch 10 of the first embodiment is given the same reference numerals as those used in the first embodiment, thereby omitting the detailed description of the configuration. The inspection patch and the test example are described in sequence below.
[0501] [Inspection patch]
[0502] Reference Figure 2 , the inspection patch is explained.
[0503] Similar to the inspection patch 10 of the first embodiment, the inspection patch of the present embodiment is a patch used for mammography, which is an example of image diagnosis using microwaves. In mammography, the inspection patch is a patch attached to the breast to be inspected.
[0504] The inspection patch 10 has the same Figure 2 The structure of the inspection patch 10 of the first embodiment described above is the same as that of the second example. The base film 11 is formed of a polyurethane resin. In this embodiment, the adhesive layer 15 is formed of a urethane adhesive. The adhesive layer 15 is laminated on the base film 11.
[0505] The inspection patch 10 of the present embodiment satisfies the following three conditions.
[0506] (Condition 5-1) In the adhesive layer 15, the peel strength with respect to a stainless steel test plate as defined in JIS Z 0237:2009 is 1.5 N / 25 mm or more and 6.0 N / 25 mm or less.
[0507] (Condition 5-2) In the base film 11 , the breaking strength specified in JIS K 7127 is higher than the peeling strength of the adhesive layer 15 .
[0508] (Condition 5-3) In the laminate composed of the base film 11 and the adhesive layer 15, the moisture permeability specified in JIS Z0208 is 750 g / m at 40° C. and a relative humidity of 90%. 2 · More than one day.
[0509] According to the inspection patch 10, by making the peel strength of the adhesive layer 15 6.0N / 25mm or less, it is possible to suppress a portion of the adhesive layer 15 from remaining on the breast. In addition, by making the breaking strength of the base film 11 higher than the peel strength of the adhesive layer 15, the base film 11 is less likely to be damaged. This can reduce the burden on the subject and the person implementing the inspection. On the other hand, in the laminate composed of the base film 11 and the adhesive layer 15, the moisture permeability specified in JIS Z 0208 is 750g / m at 40°C and a relative humidity of 90%. 2 · days or more, so that sweating of the breast can be suppressed. In addition, the peel strength of the adhesive layer 15 is 1.5N / 25mm or more, so the adhesive layer 15 can be attached to the breast in a manner that fills the height difference between the breast body and the nipple (i.e., fills the height difference between the breast body and the nipple). This can improve the accuracy of the examination.
[0510] Furthermore, since the adhesive layer 15 is formed of a urethane adhesive having high permeability among synthetic resins, sweating of the inspection object to which the adhesive layer 15 is attached can be suppressed.
[0511] The polyurethane resin used to form the base film 11 includes at least one selected from the group consisting of ether polyurethane resin, ester polyurethane resin and carbonate polyurethane resin. The base film 11 is preferably formed of ether polyurethane resin. By using ether polyurethane resin to form the base film 11, the moisture permeability of the base film 11 can be improved.
[0512] The thickness of the basement membrane 11 is preferably 20 μm or less. Thus, when the basement membrane 11 is attached to the breast, wrinkles caused by excessive thickness of the basement membrane 11 can be suppressed. In addition, the thickness of the basement membrane 11 is preferably 8 μm or more. Thus, when the basement membrane 11 is attached to the breast, wrinkles caused by excessive thinness of the basement membrane 11 can be suppressed.
[0513] The breaking strength of the base film 11 is preferably 6.3 N / 25 mm or more and 10.4 N / 25 mm or less. Thus, compared with a base film 11 having a breaking strength exceeding 10.4 N / 25 mm, the thickness of the base film 11 can be suppressed while maintaining a higher moisture permeability while suppressing damage to the base film 11.
[0514] The base film 11 is transparent or translucent. In the base film 11, the total light transmittance specified in JIS K 7361-1 is preferably 30% or more, more preferably 50% or more.
[0515] The adhesive layer 15 is transparent or translucent. The total light transmittance of the adhesive layer 15 is preferably 30% or more, and more preferably 50% or more.
[0516] In the portion of the inspection patch 10 excluding the coordinate grid 12 , the total light transmittance specified in JIS K 7361-1 is preferably 30% or more, more preferably 50% or more.
[0517] [Test example]
[0518] Reference Fig.18 , a test example of the inspection patch is described.
[0519] [Test Example 5-1]
[0520] A protective film with a thickness of 75 μm (Serapil BX-9 manufactured by Toray Film Processing Co., Ltd.) (Serapil is a registered trademark) was prepared. A urethane adhesive (Siabank SP-205 manufactured by Toyochem Co., Ltd.) (Siabank is a registered trademark) and a curing agent (T-501B manufactured by Toyochem Co., Ltd.) were prepared as a main agent. Then, the curing agent was added to the urethane adhesive so that the ratio of the number of moles of isocyanate groups contained in the curing agent to the number of moles of hydroxyl groups contained in the main agent (the number of moles of isocyanate groups / the number of moles of hydroxyl groups) (hereinafter also referred to as the molar ratio of the main agent to the curing agent) was 0.13, and they were stirred to prepare a coating liquid. Next, the coating liquid was applied to the protective film by gravure coating, and the urethane adhesive was dried. Thus, an adhesive layer with a thickness of 10 μm was obtained. Next, a urethane film with a thickness of 8 μm (manufactured by Okura Industries, Silcronn HVL85SW) (Silcronn is a registered trademark) was prepared as a base film. Then, after the base film and the adhesive layer were pasted together, they were left to stand at 50°C for 3 days. Thus, the inspection patch of Test Example 5-1 was obtained.
[0521] [Test Example 5-2]
[0522] In Test Example 5-1, except that the molar ratio of the main agent to the curing agent was changed to 0.19, a test patch of Test Example 5-2 was obtained by the same method as in Test Example 5-1.
[0523] [Test Example 5-3]
[0524] In Test Example 5-1, except that the thickness of the adhesive layer was changed to 20 μm, a test patch of Test Example 5-3 was obtained by the same method as in Test Example 5-1.
[0525] [Test Example 5-4]
[0526] In Test Example 5-2, except that the thickness of the adhesive layer was changed to 20 μm, a test patch of Test Example 5-4 was obtained by the same method as in Test Example 5-2.
[0527] [Test Example 5-5]
[0528] Prepare polypropylene (PP) laminated release paper (Lintek (strain) manufacturing, EV130TPD) as a separation membrane. Then, after coating with an aqueous polyurethane containing an ether-based polyol (Mitsui Chemicals (strain) manufacturing, Takluck WS-6021) (Takluck is a registered trademark), the aqueous polyurethane is dried. Then, by aging the dried layer at room temperature for 2 days, a base film with a thickness of 10 μm is obtained. The adhesive layer is attached to the base film to obtain the inspection patch of Test Example 5-5, wherein the adhesive layer is made by the same method as Test Example 5-1 except that the thickness is changed to 15 μm.
[0529] [Test Examples 5-6]
[0530] In Test Example 5-5, except that the thickness of the base film was changed to 15 μm, a test patch of Test Example 5-6 was obtained by the same method as in Test Example 5-5.
[0531] [Test Examples 5-7]
[0532] In Test Example 5-6, except that the thickness of the adhesive layer was changed to 20 μm and the molar ratio of the main agent to the curing agent was changed to 0.03, a test patch of Test Example 5-7 was obtained by the same method as Test Example 5-6.
[0533] [Test Example 5-8]
[0534] In Test Example 5-1, the main agent was changed to an acrylic adhesive (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., Coponel 8065) (Coponel is a registered trademark), and the curing agent was changed to a curing agent (manufactured by Tosoh Co., Ltd., Colonel L-55E) (Colonel is a registered trademark). Then, the molar ratio of the main agent to the curing agent was changed to 0.15, and the inspection patch of Test Example 5-8 was obtained by the same method as Test Example 5-1.
[0535] [Test Example 5-9]
[0536] In Test Example 5-1, except that the molar ratio of the main agent to the curing agent was changed to 0.25, a test patch of Test Example 5-9 was obtained by the same method as in Test Example 5-1.
[0537] [Test Example 5-10]
[0538] A test patch of Test Example 5-10 was obtained by the same method as Test Example 5-1 except that a PU film (ESMAR URS, manufactured by Nippon Matai Co., Ltd.) (ESMAR is a registered trademark) with a thickness of 30 μm was prepared as a base film.
[0539] [Test Example 5-11]
[0540] The inspection patch of Test 5-11 was obtained by the same method as Test Example 5-1, except that an acrylic adhesive (manufactured by Nippon Synthetic Chemical Industries, Ltd., Copolymer N-4181) and a curing agent (manufactured by Tosoh Corporation, Coronet L-55E) were prepared as the main agent and the thickness of the adhesive layer was changed to 20 μm.
[0541] [Test Example 5-12]
[0542] In Test Example 5-7, except that the molar ratio of the main agent to the curing agent was changed to 0.01, a test patch of Test Example 5-12 was obtained by the same method as in Test Example 5-7.
[0543] [Test Example 5-13]
[0544] A water transfer tattoo patch (manufactured by Slime Japan, transfer patch model: 51112) was prepared. A transparent adhesive film was formed by a PVA layer having a thickness of 5 μm and a separation layer having a thickness of 110 μm and supporting the PVA layer. The separation layer was peeled off from the transparent adhesive film, thereby using the PVA layer as a base film. Then, an adhesive layer obtained by the same method as in Test Example 5-1 was attached to the PVA layer to obtain a test patch for Test Example 5-13.
[0545] [Evaluation method]
[0546] [Breaking strength]
[0547] The breaking strength was measured according to the method of "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K 7127. When measuring the breaking strength, each test patch was demolded into a dumbbell shape with a width of 6 mm in the narrow parallel portion (test piece type 1B). Then, a tensile breaking measurement was performed using a tensile testing machine. The tensile speed was set to 300 mm / min, the distance L0 between the markings was set to 25 mm, and the tensile load at break was measured. The breaking strength when the width of the adhesive layer was 25 mm was calculated by multiplying the measured tensile load by 25 / 6. It should be noted that in the tensile breaking measurement, the tensile breaking measurement was performed on a laminate consisting only of a base film and an adhesive layer.
[0548] [Peel strength]
[0549] The peel strength of the inspection patch was measured according to the method of "Adhesive Tape / Adhesive Sheet Test Method" of JIS Z 0237:2009. Samples with a width of 25 mm were made using each inspection patch. Then, after peeling the protective film from the adhesive layer, the adhesive layer was attached to a stainless steel test plate. Next, a load was applied to the sample by moving the sample back and forth twice on a roller weighing 2 kg, and then the sample was left to stand for more than 30 minutes. Then, using a tensile tester, the peel strength was measured when the peel speed was 300 mm / min and the sample was torn off 180° relative to the stainless steel test plate.
[0550] [Moisture Permeability]
[0551] The moisture permeability of the inspection patch was measured according to the method of "Moisture permeability test method for moisture-proof packaging materials (cup method)" of JIS Z 0208. When measuring the moisture permeability, calcium chloride (anhydrous) was weighed as a moisture absorbent. Next, the initial weight of the moisture permeable cup containing the moisture absorbent was measured using an electronic balance. Then, the inspection patch was placed in an environment of 40°C and 90% relative humidity for 2 hours, and the weight of the moisture permeable cup was measured. After that, the increase in the weight of the moisture permeable cup was calculated as the amount of water vapor permeation.
[0552] [Fit adaptability]
[0553] The breast cancer palpation training model (manufactured by Tanac Co., Ltd.) was used to evaluate the fit of the inspection patch. The inspection patch was attached to the breast of the model and the following three items were evaluated.
[0554] (Item 1) Check for wrinkles on the patch
[0555] (Item 2) Inspection patch bulge
[0556] (Item 3) Degree of ease of damage of inspection patch
[0557] In item 1, when the inspection patch was attached to the breast, whether wrinkles were generated on the inspection patch was evaluated based on the following two levels.
[0558] ○: No wrinkles or slight wrinkles, but no impact on inspection
[0559] ×: Large wrinkles that may affect inspection are generated
[0560] In item 2, when the inspection patch was attached to the breast, whether a part of the inspection patch protruded from the nipple was evaluated based on the following two levels.
[0561] ○: No bulge or bulge due to uneven nipple area, but does not affect the examination
[0562] ×: The inspection patch is significantly raised from the nipple, thus affecting the inspection
[0563] In item 3, the following operations were performed: after attaching the inspection patch to the breast, the inspection patch was temporarily peeled off from the breast, and the inspection patch was attached to the breast again, and the following three levels were evaluated.
[0564] ◎: Even if the inspection patch is quickly peeled off from the breast, the basement membrane will not be damaged
[0565] ○: When the examination patch is peeled off from the breast slowly, the basement membrane will not be damaged
[0566] ×: Even if the examination patch is peeled off from the breast slowly, the basement membrane will be damaged
[0567] [Glue residue]
[0568] The adhesive layer for each inspection patch was formed on a PET film having a thickness of 12 μm as a support. Then, the adhesive layer was attached to the human body, and in this state, after more than 30 minutes, the adhesive layer was then torn off 180° relative to the human body using a tensile testing machine. At this time, the peeling speed was set to 300 mm / min. Whether there was glue residue when the adhesive layer was torn off from the human body, that is, whether a part of the adhesive layer remained on the human body, was evaluated according to the following 2 levels.
[0569] ○: No adhesive layer remains
[0570] ×: Part of the adhesive layer did not peel off but remained on the human body
[0571] [Sweating degree]
[0572] Each test patch was attached to the human body, and after 30 minutes or more, the position where each test patch was attached was checked for sweating. At this time, the degree of sweating was evaluated according to the following three levels.
[0573] ◎: No sweat at all
[0574] ○: You will sweat, but it will not affect the inspection using microwaves
[0575] ×: Sweating occurs and noise is generated in the inspection results using microwaves
[0576] [Evaluation results]
[0577] Reference Fig.18 , the results of each evaluation are explained.
[0578] like Fig.18 As shown in the figure, it can be confirmed that the moisture permeability of the laminate composed of the base film and the adhesive layer can be maintained at a high level according to the adhesive layer made of polyurethane resin with high moisture permeability. Specifically, it can be confirmed that in the laminate having the adhesive layer made of polyurethane resin, the moisture permeability of the laminate can be maintained at 750g / m 2 In addition, it can be confirmed that if the moisture permeability of the laminate is 750g / m 2 If the moisture permeability of the laminate is 850 g / m 2 · If you stay awake for more than 10 days, you will not sweat at all.
[0579] As shown in Test Examples 5-9 and 5-10, it was confirmed that even when a polyurethane resin adhesive layer was used, if the peel strength of the adhesive layer was 1.2 N / 25 mm or less, the adhesion to the height difference portion was low, and thus bulging occurred due to the height difference between the nipple portion and the breast body. On the other hand, as shown in Test Example 5-4, it was confirmed that if the peel strength of the adhesive layer was 1.6 N / 25 mm or more, bulging of the laminate could be reliably suppressed. From such results, it is preferred that the peel strength of the adhesive layer be 1.5 N / 25 mm or more, so as to suppress bulging caused by the height difference between the nipple portion and the breast body.
[0580] However, as shown in Test Example 5-12, it can be confirmed that when the peel strength of the adhesive layer is 7.2N / 25mm, the adhesiveness to the human body is too high, so when the adhesive layer is peeled off from the human body, glue residue is generated. On the contrary, as shown in Test Example 5-11, if the peel strength of the adhesive layer is 5.4N / 25mm or less, glue residue is not generated. Therefore, in terms of suppressing glue residue, the peel strength of the adhesive layer is preferably 6.0N / 25mm or less.
[0581] As described above, in order to suppress swelling of the laminate composed of the base film and the adhesive layer and to suppress adhesive residue of the adhesive layer, the peel strength of the adhesive layer is preferably 1.5 N / 25 mm to 6.0 N / 25 mm.
[0582] In addition, it can be confirmed that the thickness of the base film is positively correlated with the fracture strength of the base film. Then, as shown in Test Examples 5-5 to 5-7, in terms of suppressing the damage of the base film generated when peeling off the base film, it can be said that it is preferred that the fracture strength is greater than the peeling strength, and the difference between the fracture strength and the peeling strength is larger. However, as shown in Test Example 5-10, when the base film is too thick and the rigidity of the base film itself is too high, wrinkles are easily generated on the base film when the base film is attached. In addition, when the rigidity of the base film is too high, even after the force on the base film is released, it is easy to maintain the shape change when peeling off the base film as a deformation of the base film. From this aspect, the thickness of the base film is preferably less than 30μm, and more preferably less than 20μm.
[0583] On the contrary, as shown in Test Example 5-13, even when the thickness of the base film is too thin, wrinkles are easily generated on the base film when the base film is attached. Therefore, the thickness of the base film is preferably greater than 5 μm, and more preferably greater than 8 μm.
[0584] In addition, as shown in Test Examples 5-1 to 5-8, if the breaking strength of the base film is within the range of 6.3 N / 25 mm to 10.4 N / 25 mm, the breakage of the base film can be suppressed, and the thickness of the base film can be suppressed within the range of maintaining the high moisture permeability of the base film.
[0585] In summary, according to the fifth embodiment of the inspection patch, the following advantages can be obtained.
[0586] (5-1) By setting the peel strength of the adhesive layer 15 to 6.0 N / 25 mm or less, it is possible to prevent a portion of the adhesive layer 15 from remaining on the breast B. In addition, since the breaking strength of the basement membrane 11 is higher than the peel strength of the adhesive layer 15, the basement membrane 11 is less likely to be damaged. This can reduce the burden on the examinee and the examiner.
[0587] (5-2) In the laminate consisting of the base film 11 and the adhesive layer 15, the moisture permeability is 750 g / m 2 · days or more, so it is possible to suppress sweating of the breast B. In addition, the peel strength of the adhesive layer 15 is 1.5N / 25mm or more, so the adhesive layer 15 can be attached to the breast B in a manner that fills the height difference of the breast B (i.e. fills the height difference of the breast B). This can improve the accuracy of the examination.
[0588] (5-3) The adhesive layer 15 is formed of a urethane adhesive having high moisture permeability among synthetic resins, and thus sweating of the breast B can be suppressed.
[0589] (5-4) By setting the thickness of basement membrane 11 to be 20 μm or less, when basement membrane 11 is attached to breast B, wrinkles on basement membrane 11 due to excessive thickness of basement membrane 11 can be suppressed.
[0590] (5-5) By setting the thickness of basement membrane 11 to be 8 μm or more, when basement membrane 11 is attached to breast B, wrinkles on basement membrane 11 due to excessively thin basement membrane 11 can be suppressed.
[0591] (5-6) By forming the base film 11 using an ether-based polyurethane resin, the moisture permeability of the base film 11 can be improved.
[0592] (5-7) By making the breaking strength of the base film 11 greater than 6.3 N / 25 mm and less than 10.4 N / 25 mm, compared with the base film 11 having a breaking strength exceeding 10.4 N / 25 mm, the thickness of the base film 11 can be suppressed while maintaining a higher moisture permeability range while suppressing damage to the base film 11.
[0593] [Variation of the fifth embodiment]
[0594] It should be noted that the fifth embodiment described above may be modified as follows.
[0595] [Basement membrane]
[0596] The base film 11 may be formed of a polyurethane resin other than the ether polyurethane resin. For example, the base film 11 may be formed of an ester polyurethane resin or a carbonate polyurethane resin.
[0597] As long as the laminate of the base film 11 and the adhesive layer 15 included in the inspection patch 10 satisfies the above-mentioned conditions 5-1 to 5-3, the synthetic resin used to form the base film 11 may be a resin other than the polyurethane resin.
[0598] The thickness of the base film 11 may be greater than 20 μm or less than 8 μm. Even in this case, as long as the inspection patch 10 satisfies conditions 5-1 to 5-3, the advantages based on the above (5-1) and (5-2) can be obtained.
[0599] The breaking strength of the base film 11 may be less than 6.3 N / 25 mm or may exceed 10.4 N / 25 mm. Even in this case, as long as the inspection patch 10 satisfies conditions 5-1 to 5-3, the advantages based on the above (5-1) and (5-2) can be obtained.
[0600] [Adhesive layer]
[0601] The adhesive used to form the adhesive layer 15 may be an adhesive other than a urethane adhesive. For example, according to Test Example 5-8, the adhesive used to form the adhesive layer 15 may be an acrylic adhesive. Even in this case, as long as the above conditions 5-1 to 5-3 are satisfied, the advantages based on the above (5-1) and (5-2) can be obtained.
[0602] [Separation membrane]
[0603] The separation film 13 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 and the adhesive layer 15 satisfying the above conditions 5-1 to 5-3, the advantages based on the above (5-1) and (5-2) can be obtained.
[0604] [Protective film]
[0605] The protective film 14 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 and the adhesive layer 15 satisfying the above conditions 5-1 to 5-3, the advantages based on the above (5-1) and (5-2) can be obtained.
[0606] [Inspection patch]
[0607] In the inspection patch 10, the total light transmittance only needs to be 50% or more in at least the portion of the laminate composed of the base film 11 and the adhesive layer 15 except for the coordinate grid 12. In this case, by peeling off the separation film 13 from the base film 11 and peeling off the protective film 14 from the adhesive layer 15, the coordinate grid 12 of the base film 11 can be observed.
[0608] It should be noted that in the inspection patch 10, the total light transmittance can be 50% or more in the portion of the laminate composed of the separation film 13, the base film 11 and the adhesive layer 15 except for the coordinate grid 12. Therefore, when the inspection patch 10 is attached to the inspection object, the coordinate grid 12 of the base film 11 can be observed regardless of whether the separation film 13 is peeled off from the base film 11 or not.
[0609] Supplement the technical ideas grasped from the above-mentioned implementation methods.
[0610] [Addendum 5-1]
[0611] A method for manufacturing a patch for inspection,
[0612] The invention relates to a method for producing a test patch having a base film and an adhesive layer laminated on the base film.
[0613] comprising the step of forming the adhesive layer,
[0614] The process of forming the adhesive layer includes: mixing a main agent and a curing agent, wherein the main agent includes a main chain composed of a carbamate skeleton and having at least two ends and a hydroxyl group at each end of the main chain; the curing agent includes a main chain composed of a carbamate skeleton and having at least two ends and an isocyanate group at each end of the main chain, so that the ratio of the molar number of the isocyanate group to the molar number of the hydroxyl group is greater than 0.02 and less than 0.2.
[0615] (5-8) According to the above-mentioned structure, the peel strength of the adhesive layer is increased to a level that can follow the height difference of the inspection object to fill the height difference of the inspection object (that is, fill the height difference of the inspection object), and is reduced to a level that a portion of the adhesive layer will not remain on the inspection object when the adhesive layer is peeled off from the inspection object.
[0616] [Sixth embodiment]
[0617] Reference Figure 2 and Fig.19 , a sixth embodiment of the inspection patch is described. In the sixth embodiment, the configuration common to the inspection patch 10 of the first embodiment is given the same reference numerals as those used in the first embodiment, thereby omitting the detailed description of the configuration. The inspection patch and the test example are described in sequence below.
[0618] [Inspection patch]
[0619] Reference Figure 2 , the inspection patch is described. Like the inspection patch 10 of the first embodiment, the inspection patch of this embodiment is a patch for mammography, which is an example of image diagnosis using microwaves. In mammography, the inspection patch is a patch attached to the breast as the inspection object.
[0620] The inspection patch 10 has the same Figure 2 The structure is the same as the second example of the inspection patch 10 of the first embodiment described above. In the inspection patch 10 of the present embodiment, the laminate composed of the base film 11 and the adhesive layer 15 satisfies the following two conditions.
[0621] (Condition 6-1) Tensile elongation at break is 130% or more
[0622] (Condition 6-2) 100% modulus of tensile stress is 10 MPa or less
[0623] In addition, in the inspection patch 10, the base film 11 satisfies the following conditions.
[0624] (Condition 6-3) The peel strength of the surface of the base film 11 opposite to the surface on which the adhesive layer 15 is formed with respect to the stainless steel plate is 3.5 N / 25 mm or less.
[0625] According to the inspection patch 10, the tensile elongation at break of the laminate is 130% or more, and the 100% tensile stress is 10 MPa or less, so the laminate composed of the base film 11 and the adhesive layer 15 can be greatly stretched by a small force. In addition, since the peel strength of the base film 11 is 3.5 N / 25 mm or less, the flexibility of the laminate can be kept high as described above, and when a part of the laminate contacts other parts, the contact in the laminate can be released by applying force in a direction away from the contact part. Thus, the laminate that matches the breast can be easily attached by the flexibility of the laminate, and the contact in the laminate can also be easily released, thereby improving the operability of the inspection patch 10.
[0626] The tensile elongation at break is calculated according to "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K 7127:1999 (ISO 527-3:1995) and "Plastics - Calculation methods for tensile properties - Part 1: General" of JIS K 7161-1:2014 (ISO 527-1:2012). When the test piece as the object of measurement has no yield point, the "tensile fracture strain" defined in 3.7.2 of JIS K 7161-1:2014 is calculated as the tensile fracture elongation. On the other hand, when the test piece has a yield point, the "tensile fracture nominal strain" defined in 3.8.1 of the standard is calculated as the tensile fracture elongation. It should be noted that the tensile fracture strain is calculated according to the following formula (1) described in 10 "Calculation and expression of test results" of the standard. The tensile break nominal strain is calculated according to the following formula (2) described in 10 "Calculation and expression of test results" of the standard.
[0627] ε=ΔL0 / L0 ···Formula (1)
[0628] ε t =ε y +ΔL t / L···Formula (2)
[0629] It should be noted that in formula (1), ε is the strain (%), L0 is the distance between the markings of the test piece (mm), and ΔL0 is the increase in the distance between the markings of the test piece (mm). t is the nominal strain (%), ε y is the yield strain (%), L is the initial distance between the clamps (mm), ΔL tis the increase in the distance between the clamps from the yield point (mm).
[0630] According to "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K 7127:1999 (ISO 527-3:1995), the 100% tensile stress is calculated as the stress when the strain reaches the specified value (100%) in "x% strain tensile stress" defined in 3.6.3 of "Plastics - Calculation methods for tensile properties - Part 1: General" of JIS K 7161-1:2014 (ISO 527-1:2012). It should be noted that the 100% strain tensile stress is calculated according to the following formula (3) described in 10 "Calculation and expression of test results" of the standard.
[0631] σ=F / A ···Formula (3)
[0632] It should be noted that in formula (3), σ is stress (MPa), F is the magnitude of the force to be measured (N), and A is the initial cross-sectional area of the test piece (mm 2 ).
[0633] The peel strength was measured according to the method of "Testing methods for adhesive tapes / adhesive sheets" of JIS Z 0237: 2009. The peel strength was measured as "Method 1: Adhesion strength at 180° peeling relative to a test plate" in 10.4.1 of the standard.
[0634] The base film 11 is formed of a polyurethane resin. The polyurethane resin preferably includes at least one selected from the group consisting of an ether polyurethane resin, an ester polyurethane resin, and a carbonate polyurethane resin. Thus, a base film 11 having high flexibility and being easily attached to the inspection object can be obtained.
[0635] Ether polyurethane resin refers to a polyurethane resin generated using an ether polyol containing an ether bond (-O-). Ester polyurethane resin refers to a polyurethane resin generated using an ester polyol containing an ester bond (-COO-). Carbonate polyurethane resin refers to a polyurethane resin generated using a polyol containing a carbonate bond (-OC(=O)O-). The thickness of the base film 11 is preferably not less than 5 μm and not more than 30 μm.
[0636] The polyurethane resin may include a first polyurethane resin and a second polyurethane resin. The glass transition temperature of the first polyurethane resin is lower than the glass transition temperature of the second polyurethane resin. By making the polyurethane resin forming the base film 11 include two polyurethane resins having different glass transition temperatures, the base film 11 can have both flexibility and low adhesion. Among the polyurethane resins forming the base film 11, the first polyurethane resin having a low glass transition temperature tends to mainly contribute to the flexibility of the base film 11, and the second polyurethane resin having a high glass transition temperature tends to mainly contribute to the low adhesion of the base film 11.
[0637] The glass transition temperature of the first polyurethane resin may be 40° C., and the glass transition temperature of the second polyurethane resin may be 90° C. Thus, the difference between the glass transition temperatures of the first polyurethane resin and the second polyurethane resin is large, so that the base film can easily have both flexibility and low adhesion.
[0638] The inspection patch 10 is often used in an environment where the temperature is kept at room temperature, i.e., about 20°C. In this case, the difference between the glass transition temperature of the first polyurethane resin and the ambient temperature is small, and the glass transition temperature of the second polyurethane resin is much higher than the ambient temperature. Thus, the first polyurethane resin can improve the softness of the base film, and the second polyurethane resin can reduce the adhesiveness of the base film.
[0639] The ratio (P2 / P1) of the second mass (P2) of the second polyurethane resin to the first mass (P1) of the first polyurethane resin is preferably 1 / 25 or more and 1 / 5 or less. Thus, by the ratio of the first mass to the second mass, the tensile elongation at break and 100% tensile stress for achieving high flexibility and the peel strength for achieving low adhesion can be exhibited in the base film 11.
[0640] The adhesive layer 15 is formed of an adhesive made of a synthetic resin. The adhesive layer 15 is preferably formed of a urethane adhesive. When the adhesive layer 15 is formed of a urethane adhesive, the thickness of the adhesive layer 15 is preferably 5 μm or more and 25 μm or less.
[0641] The separation film 13 and the protection film 14 are preferably films made of a transparent or translucent synthetic resin.
[0642] The hardness of the separation membrane 13 is preferably higher than the hardness of the base membrane 11. Thus, when a part of the separation membrane 13 is in contact with another part, adhesion of the contacting parts to each other can be suppressed.
[0643] As described above, since the laminate satisfies conditions 6-1 and 6-2, the amount by which the laminate is stretched is large relative to the force acting on the laminate. Therefore, the laminate has a high ability to follow the shape of the breast B, and wrinkles are not easily generated on the laminate. Moreover, since the basement membrane 11 satisfies condition 6-3, when the laminate is stretched, even if a part of the basement membrane 11 contacts other parts, or a part of the adhesive layer 15 contacts other parts, such contact can be released. In this way, since the laminate composed of the basement membrane 11 and the adhesive layer 15 has high flexibility but low adhesion, the inspection efficiency of mammography can be improved according to the inspection patch 10 having such a laminate.
[0644] [Test example]
[0645] Reference Fig.19 , the test example is described.
[0646] [Test Example 6-1]
[0647] A PET film (manufactured by Toray Fine Chemicals Co., Ltd., Celapil BX-9) (Celapil is a registered trademark) having a release layer and a thickness of 75 μm was prepared as a separation membrane. Then, an aqueous polyurethane containing an ether polyol (manufactured by Mitsui Chemicals Co., Ltd., Takluck WS-6021) (Takluck is a registered trademark) was applied to the separation membrane and then dried. Next, the dried layer was aged at room temperature for 2 days to obtain a base film with a thickness of 10 μm.
[0648] Next, a PET film (manufactured by Toray Film Processing Co., Ltd., Celapil WZ) with a release layer and a thickness of 38 μm was prepared as a protective film. 1% of a curing agent (manufactured by Toray Film Co., Ltd., T-501B) was added to a urethane adhesive (manufactured by Toray Film Co., Ltd., SP-205), and they were stirred to prepare a coating solution. Then, the coating solution was applied to the protective film using gravure coating, and the urethane adhesive was dried. Thus, an adhesive layer with a thickness of 20 μm was obtained. Then, a laminate was obtained by pasting the base film and the adhesive layer together. The inspection patch of Test Example 6-1 was obtained by aging the laminate in an environment of 40°C.
[0649] [Test Example 6-2]
[0650] An aqueous polyurethane having a glass transition temperature of 40°C and containing an ether polyol (manufactured by Mitsui Chemicals, Inc., TAKELACK WS-6021) was prepared as the first polyurethane resin. An aqueous polyurethane having a glass transition temperature of 90°C and containing an ether polyol (manufactured by Mitsui Chemicals, Inc., TAKELACK W-6020) was prepared as the second polyurethane resin. Then, the first polyurethane resin and the second polyurethane resin were mixed so that the ratio of the mass of the second polyurethane resin to the mass of the first polyurethane resin was 1 / 25. In Test Example 6-1, a polyurethane resin obtained by mixing the first polyurethane resin and the second polyurethane resin was used, and the inspection patch of Test Example 6-2 was obtained by the same method as Test Example 6-1.
[0651] [Test Example 6-3]
[0652] In Test Example 6-2, except that the ratio of the mass of the second polyurethane resin to the mass of the first polyurethane resin was changed to 1 / 12.5, a test patch of Test Example 6-3 was obtained by the same method as in Test Example 6-2.
[0653] [Test Example 6-4]
[0654] In Test Example 6-2, except that the ratio of the mass of the second polyurethane resin to the mass of the first polyurethane resin was changed to 1 / 10, a test patch of Test Example 6-4 was obtained by the same method as in Test Example 6-2.
[0655] [Test Example 6-5]
[0656] In Test Example 6-2, except that the ratio of the mass of the second polyurethane resin to the mass of the first polyurethane resin was changed to 1 / 5, a test patch of Test Example 6-5 was obtained by the same method as in Test Example 6-2.
[0657] [Test Example 6-6]
[0658] In Test Example 6-2, except that the ratio of the mass of the second polyurethane resin to the mass of the first polyurethane resin was changed to 1 / 2, a test patch of Test Example 6-6 was obtained by the same method as in Test Example 6-2.
[0659] [Test Examples 6-7]
[0660] In Test Example 6-2, except that the mass of the first polyurethane resin and the mass of the second polyurethane resin were changed to be the same, a test patch of Test Example 6-7 was obtained by the same method as in Test Example 6-2.
[0661] [Test Examples 6-8]
[0662] In Test Example 6-2, except that the ratio of the mass of the second polyurethane resin to the mass of the first polyurethane resin was changed to 5 / 1, a test patch of Test Example 6-8 was obtained by the same method as in Test Example 6-2.
[0663] [Test Examples 6-9]
[0664] In Test Example 6-2, except that the mass of the second polyurethane resin was changed to 10 / 1 with respect to the mass of the first polyurethane resin, a test patch of Test Example 6-9 was obtained by the same method as in Test Example 6-2.
[0665] [Evaluation method]
[0666] [Tensile elongation at break]
[0667] The tensile elongation at break was measured according to the method of "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K 7127:1999 (ISO 527-3:1995) and "Plastics - Calculation methods for tensile properties - Part 1: General" of JIS K 7161-1:2014 (ISO 527-1:2012). When measuring the tensile elongation at break, the inspection patch was demolded into a dumbbell shape (test piece type 5), and the tensile elongation at break was measured using a tensile testing machine (AGS-X 5kN manufactured by Shimadzu Corporation). The test speed was set to 300 mm / min, the distance between the markings L0 was set to 25 mm, and the initial distance between the clamps L was set to 80 mm. In the case where the test piece has no yield point, the tensile fracture strain is calculated as the tensile fracture elongation. On the other hand, in the case where the test piece has a yield point, the tensile fracture nominal strain is calculated as the tensile fracture elongation. In addition, when measuring the tensile elongation at break, the measurement was performed on the laminate consisting of only the base film and the adhesive layer.
[0668] [100% modulus of tensile stress]
[0669] Similar to the measurement of tensile elongation at break, test pieces were prepared according to "Plastics - Test conditions for tensile properties - Part 3: Test methods for films and sheets" of JIS K 7127:1999 (ISO527-3:1995). Then, 100% tensile stress was calculated as the stress when the strain reached 100% according to "Plastics - Calculation methods for tensile properties - Part 1: General" of JIS K7161-1:2014 (ISO527-1:2012).
[0670] [Fit adaptability]
[0671] The fit of the inspection patch was evaluated using a breast cancer palpation training model (manufactured by Tanak Co., Ltd.). The inspection patch was attached to the breast of the model, and the presence of wrinkles on the inspection patch was evaluated based on the following three levels. It should be noted that among the following three levels, the inspection patch evaluated as "○" or "△" is an inspection patch with good fit.
[0672] ○: No wrinkles
[0673] △: Slight wrinkles are produced, but they do not affect the inspection
[0674] ×: Large wrinkles that may affect inspection are generated
[0675] [Peel strength]
[0676] According to the method of "Adhesive tape / adhesive sheet test method" of JIS Z 0237:2009, the peel strength was measured. In the determination of peel strength, a desktop precision universal testing machine ((strain) Shimadzu Manufacturing, AGS-X 5kN) and a SUS304 plate with surface finishing BA were used. A test piece with a width of 25mm was made from the inspection patch. Then, in the base film, the surface on the opposite side of the surface laminated with the adhesive layer was contacted with the SUS plate, and the base film was crimped onto the SUS plate using a 2kg rubber roller. Then, the test speed was set to 300mm / minute, and the test piece was peeled off 180° from the SUS plate.
[0677] [Processing adaptability]
[0678] In a laminate composed of a base film and an adhesive layer, a first part, which is a part of the base film, was overlapped with a second part, which is another part, and then whether the base film was attached was evaluated based on the following three levels. It should be noted that in the following three levels, an inspection patch evaluated as "○" or "△" is an inspection patch with processing adaptability.
[0679] ○: Part 1 and Part 2 are not attached
[0680] △: The first part and the second part are attached, but even if the second part is peeled off from the first part, the base film is not damaged.
[0681] ×: The first part and the second part are attached, and when the second part is peeled off from the first part, the basement membrane is damaged
[0682] [Evaluation results]
[0683] Reference Fig.19 , the results of each evaluation are explained.
[0684] like Fig.19As shown, it can be confirmed that in all the inspection patches of Test Examples 6-1 to 6-9, the tensile elongation at break is more than 130%. In addition, it can be confirmed that in the inspection patches of Test Examples 6-1 to 6-5, the 100% tensile stress is less than 10 MPa. On the contrary, it can be confirmed that in the inspection patches of Test Examples 6-6 to 6-9, the 100% tensile stress is greater than 10 MPa. In addition, it can be confirmed that in the evaluation of the fit adaptability, the evaluation results of the inspection patches of Test Examples 6-1 to 6-4 are "○", the evaluation results of the inspection patches of Test Example 6-5 are "△", and the evaluation results of the inspection patches of Test Examples 6-6 to 6-9 are "×".
[0685] As described above, it can be confirmed that according to the inspection patches of Test Examples 6-1 to 6-4, high fit adaptability can be obtained by making the tensile elongation at break a high value of more than 440% and making the 100% tensile stress a low value of less than 4.2MPa. In addition, in Test Example 6-5, the tensile elongation at break is a high value of 450%. On the other hand, although the 100% tensile stress is less than 10MPa, it is higher than the value of the inspection patches of Test Examples 6-1 to 6-4, so wrinkles that do not affect the inspection are confirmed in the laminate. On the contrary, it can be confirmed that in the inspection patches of Test Examples 6-6 to 6-9, the tensile elongation at break is a high value of more than 330%. On the other hand, the 100% tensile stress is also a high value exceeding 10MPa. Therefore, in the inspection patches of Test Examples 6-6 to 6-9, a large force is required to stretch the inspection patches, and thus it is difficult to attach the laminate to the breast without causing wrinkles.
[0686] In addition, it was confirmed that in the inspection patch of Test Example 6-1, since the peel strength was a high value of 3.6 N / 25 mm, the base film was damaged when the second part of the base film was peeled off from the first part. On the other hand, it was confirmed that in the inspection patches of Test Examples 6-2 to 6-9, the second part of the base film could be peeled off from the first part by setting the peel strength to a low value of 2.2 N / 25 mm or less.
[0687] As described above, it was confirmed that the sticking suitability and handling suitability of the inspection patch can be improved simultaneously by setting the tensile elongation at break to 130% or more, the 100% modulus to 10 MPa or less, and the peel strength to 3.5 N / 25 mm or less.
[0688] In addition, according to Fig.19The recorded results show that: in the polyurethane resin used to form the base film, the higher the proportion of the second polyurethane resin with a relatively high glass transition temperature, the lower the peel strength, and thus the handling characteristics tend to become higher. However, in the polyurethane resin used to form the base film, when the proportion of the second polyurethane resin is too high, the 100% tensile stress increases, and thus the bonding adaptability tends to decrease. Then, by making the ratio (P2 / P1) of the mass of the second polyurethane resin (P2) to the mass of the first polyurethane resin (P1) be greater than 1 / 25 and less than 1 / 5, the bonding adaptability and handling characteristics of the inspection patch can be improved at the same time.
[0689] In summary, according to the sixth embodiment of the inspection patch, the advantages described below can be obtained.
[0690] (6-1) Since the tensile elongation at break is 130% or more and the 100% modulus of elongation is 10 MPa or less, the laminate composed of the base film 11 and the adhesive layer 15 can be greatly stretched with a small force. In addition, since the peel strength of the base film 11 is 3.5 N / 25 mm or less, the flexibility of the laminate can be maintained at a high level, and when a part of the laminate is in contact with another part, the contact in the laminate can be released by applying a force in a direction away from the contacting part.
[0691] (6-2) By making the polyurethane resin include at least one selected from the group consisting of ether polyurethane resins, ester polyurethane resins, and carbonate polyurethane resins, a basement membrane 11 having high flexibility and being easily adhered to the breast B can be obtained.
[0692] (6-3) By making the polyurethane resin forming the base film 11 include two types of polyurethane resins having different glass transition temperatures, the base film 11 can have both flexibility and low adhesiveness.
[0693] (6-4) By increasing the difference between the glass transition temperature of the first polyurethane resin and the glass transition temperature of the second polyurethane resin, it is easy to make the base film 11 have both flexibility and low adhesiveness.
[0694] (6-5) Since the ratio of the second mass to the first mass is greater than 1 / 25 and less than 1 / 5, the ratio of the first mass to the second mass can achieve a tensile elongation at break and 100% tensile stress for achieving high flexibility, and a peel strength for achieving low adhesion in the base film 11.
[0695] (6-6) Since the laminate composed of the base film 11 and the adhesive layer 15 is sandwiched between the separation film 13 and the protective film 14, the laminate can be kept clean by these films until the separation film 13 and the protective film 14 are peeled off from the laminate.
[0696] It should be noted that the sixth embodiment described above may be modified as follows.
[0697] [Adhesive layer]
[0698] As long as the laminate of the base film 11 and the adhesive layer 15 included in the inspection patch 10 satisfies the above-mentioned conditions 6-1 to 6-3, the adhesive used to form the adhesive layer 15 may be an adhesive other than the urethane adhesive.
[0699] [Separation membrane]
[0700] The separation film 13 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 and the adhesive layer 15 and satisfies the conditions 6-1 to 6-3, the advantage based on the above-mentioned (6-1) can be obtained.
[0701] [Protective film]
[0702] The protective film 14 may be omitted. Even in this case, as long as the inspection patch 10 includes the base film 11 and the adhesive layer 15 and satisfies the conditions 6-1 to 6-3, the advantage based on the above-mentioned (6-1) can be obtained.
[0703] [Other Modifications]
[0704] The configurations of the first to sixth embodiments and the modifications of the embodiments described above may be combined and implemented within a range where no contradiction occurs.
Claims
1. A patch for inspection, which is a patch for inspection used for image diagnosis using microwaves, comprising a patch body to be attached to an inspection object, The patch body is configured to display an index for scanning the inspection object on the patch body, to deform along with the shape of the inspection object, and to have a transmittance of 70% or more for microwaves with a frequency of 2 GHz. The patch body has: Basement membrane, and an adhesive layer laminated on the base film and attached to the inspection object, The indicator is configured to be displayed on the basement membrane. The basement membrane comprises: a back surface which is in contact with the adhesive layer, and a surface which is the surface opposite to the back surface and is scanned by the probe during inspection of the inspection object, On the surface of the base film, the arithmetic mean roughness Ra specified in JIS B 0601:2013 is 0.1 μm or more and less than 5.0 μm; and as a dynamic friction coefficient specified in JIS K 7125:1999, the dynamic friction coefficient between the surface and the metal surface is 3 or less, The invention further comprises a separation membrane having a coated surface formed of a polypropylene resin or a polyethylene resin, wherein the coated surface has an arithmetic mean roughness Ra specified in JIS B 0601:2013 of 0.2 μm or more and less than 7.0 μm, The surface of the base film is a surface in contact with the surface to be coated, and has a shape following the surface to be coated.
2. The inspection patch according to claim 1, wherein: The patch body includes a portion having a total light transmittance of 30% or more as specified in JIS K 7361-1:1997.
3. The inspection patch according to claim 1 or claim 2, wherein: The indicator has a coordinate grid.
4. The inspection patch according to claim 3, wherein: The coordinate grid includes a plurality of grid lines extending along a first direction for scanning the inspection object and arranged along a second direction perpendicular to the first direction. The plurality of grid lines include first grid lines having a first color and second grid lines having a second color different from the first color, and the first grid lines and the second grid lines are alternately arranged along the second direction.
5. The inspection patch according to claim 1, wherein: The thickness of the adhesive layer is not less than 5 μm and not more than 25 μm. In the inspection patch, in the laminate of the base film and the adhesive layer, the tensile elongation at break specified in JIS K 7127 is 130% or more, 100% tensile stress is less than 10MPa, At 40°C and 90% relative humidity, the moisture permeability specified in JIS Z 0208 is 750g / m 2 · More than one day.
6. The inspection patch according to claim 1, wherein: The adhesive layer has a peel strength as specified in JIS Z 0237:2009 with respect to a stainless steel test plate of 1.5 N / 25 mm or more and 6.0 N / 25 mm or less, In the base film, the breaking strength specified in JIS K 7127 is higher than the peel strength of the adhesive layer, In the laminate of the base film and the adhesive layer, the moisture permeability specified in JIS Z0208 is 750 g / m 2 · More than one day.
7. The inspection patch according to claim 1, wherein: The base film comprises a polyurethane resin, In the laminate of the base film and the adhesive layer, the tensile elongation at break is 130% or more, and the 100% modulus of elongation is 10 MPa or less, The peel strength with respect to the stainless steel plate on the surface of the base film opposite to the surface on which the adhesive layer is formed is 3.5 N / 25 mm or less.
8. The inspection patch according to claim 7, wherein: The polyurethane resin includes a first polyurethane resin and a second polyurethane resin, and a glass transition temperature of the first polyurethane resin is lower than a glass transition temperature of the second polyurethane resin.
9. The inspection patch according to any one of claims 5 to 8, further comprising: a separation film which is laminated in a releasable manner on the surface of the base film opposite to the surface in contact with the adhesive layer, and A protective film is laminated in a releasable manner on a surface of the adhesive layer opposite to a surface in contact with the base film.
10. The inspection patch according to claim 1, The base film has a tensile elongation at break of more than 130% and a 100% tensile strength of less than 4 N / cm. The thickness of the adhesive layer is not less than 5 μm and not more than 25 μm. In the inspection patch, in the laminate of the base film and the adhesive layer, At 40°C and 90% relative humidity, the moisture permeability specified in JIS Z 0208 is 750g / m 2 · More than one day, The adhesive layer is formed of a urethane adhesive.
11. The inspection patch according to claim 10, wherein: The base film is formed of polyurethane resin, The polyurethane resin includes at least one selected from the group consisting of ether polyurethane resins, ester polyurethane resins, and carbonate polyurethane resins.
12. The inspection patch according to claim 10, further comprising a fluidized layer stacked on the base membrane, The fluidized layer is formed of an aliphatic hydrocarbon having a higher microwave transmittance than water, and has a viscosity capable of attaching the base film to the inspection object. The aliphatic hydrocarbon is selected from the group consisting of paraffin, squalane and ceresin, The shear viscosity of the fluidized bed at 30° C. is not less than 1000 mPa·s and not more than 200000 mPa·s.
Citation Information
Patent Citations
Imaging method and imaging apparatus
WO2017057524A1
Multi-spectral, selectively reflective construct
CN102159915A
Adhesive skin patch material and roll body of adhesive skin patch material
CN107693839A
Solid ultrasonic biomedical couplant sheet
EP0800788A1
Patch for skin during anticancer drug treatment
JP2010018564A